Adhesive sheet and method for peeling adhesive sheet

By introducing thermal polymerization initiator, polymer and multifunctional monomer into the adhesive, the problem of poor peelability of existing adhesives at high temperatures is solved, and the stability and peelability of the adhesives under high temperature conditions is achieved. and preservation stability.

CN119487143APending Publication Date: 2025-02-18NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380051372.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-30
Filing Date
2023-07-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

It is difficult for the existing adhesive to maintain good peelability after heating at high temperature, which easily leads to adsorption of the adhesive on the surface of the adhered, increasing the peeling force and possibly producing residual glue.

Method used

A thermosetting adhesive containing a thermal polymerization initiator was developed, and by adding polymer, multifunctional monomer and thermal polymerization initiator to the adhesive, it ensures that good peelability can be maintained under high temperature conditions. The specific implementation method includes using an acrylic polymer and a multifunctional acrylate monomer in the adhesive layer, and controlling the self-accelerated decomposition temperature (SADT) of the thermal polymerization initiator and the content of the multifunctional monomer to optimize the bonding. The agent is easy to peel and storage stability by heating.

Benefits of technology

The stable and easy peelability of the adhesive under high temperature conditions is achieved, and good performance is maintained during long-term storage, avoiding the problems of adhesive adsorption and residual glue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487143A_ABST
    Figure CN119487143A_ABST
Patent Text Reader

Abstract

Provided is an adhesive sheet which is easy to peel off when heated and has good storage stability. The adhesive sheet has an adhesive layer. The adhesive layer contains a polymer, a polyfunctional monomer, and a thermal polymerization initiator. In addition, the self-accelerated decomposition temperature (SADT) [DEG C] of the thermal polymerization initiator satisfies the formula: SADT + 10 > = 60. In addition, the release force reduction rate A [%] after heating of the adhesive sheet is higher than 50% and lower than 99.9%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet and a method for peeling the adhesive sheet.

[0002] This application claims priority based on Japanese Patent Application No. 2022-120901 filed on July 28, 2022 and Japanese Patent Application No. 2023-011970 filed on January 30, 2023, the entire contents of which are incorporated herein by reference. Background Art

[0003] Generally, adhesives (also called pressure-sensitive adhesives. The same applies hereinafter) have the following properties: they are in a soft solid (viscoelastic) state in a temperature range near room temperature, and are easily adhered to an adherend by pressure. In view of the excellent operability of pasting to an adherend, adhesives are widely used in various fields in the form of an adhesive sheet with an adhesive layer on a support, or in the form of an adhesive sheet without a support. Among such adhesives, there are adhesives that are used by adhering to an adherend and are removed from the adherend after the purpose of the bonding is completed. As prior art documents disclosing such prior art, Patent Documents 1 to 4 can be cited. Patent Documents 1 to 4 disclose thermosetting adhesives.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-29105

[0007] Patent Document 2: Japanese Patent Application Publication No. 2016-204617

[0008] Patent Document 3: Japanese Patent Application Publication No. 2019-56101

[0009] Patent Document 4: Japanese Patent Application Publication No. 10-209087

[0010] Non-patent literature

[0011] Non-patent literature 1: Simone Napolitano, 'Irreversible adsorption of polymer melts and nanoconfinement effects', SoftMatter, 2020, 16, pp. 5348-5365

[0012] Non-Patent Document 2: Ben O'Shaughnessy and Dimitrios Vavylonis, 'Non-Equilibrium in Adsorbed Polymer Layers', J. Phys.: Condens. Matter, 17, 2005, pp. R63-99 Summary of the invention

[0013] Problems to be solved by the invention

[0014] For adhesives used for peeling and removing from adherends, it is required to have good adhesion during adhesion to the adherend and to be easily peeled from the adherend after the purpose of adhesion is completed. For example, for adhesives suitable for adherends to be treated by heat, it is expected to have easy peelability that can be easily peeled from the adherend after being heated in a state of being adhered to the adherend. However, if adherends such as glass and metal are heated at high temperature in a state of being adhered with an adhesive, there is a risk of undesirable conditions such as the adhesive being adsorbed on the surface of the adherend, thereby increasing the peeling force (heavy peeling), reducing the peeling property, or generating residual adhesive. In this regard, see the various polymers described in non-patent documents 1 to 2 that have adsorption force by heating. For example, in the case of thermosetting adhesives such as those described in patent documents 1 to 4, it is difficult to make the curing of the adhesive during high-temperature heating appear before the adsorption of the adhesive to the adherend, and the peeling force reduction and peeling force increase suppression based on the curing of the adhesive cannot be obtained, and stable easy peelability cannot be obtained after high-temperature heating.

[0015] Based on such background, the inventor of the present application has conducted research and development with an eye on a thermosetting adhesive containing a thermal polymerization initiator in the adhesive. As a result, an adhesive having easy peelability (heat peelability) after being attached to an adherend and heated at a high temperature has been successfully obtained. The above-mentioned heat peelability is usually also easy to peel after a heating treatment in which the peeling force rises, and is therefore also referred to as heat-resistant peelability. However, the above-mentioned adhesive having easy peelability due to heat polymerization initiator contains the following risk: due to long-term storage, temperature changes during storage, etc., the thermal polymerization initiator will decompose during storage, and the desired heat peelability cannot be exerted. Further in-depth research has been conducted on this, and as a result, an adhesive having easy peelability due to heat and excellent storage stability has been successfully produced, thereby completing the present invention. That is, the present invention provides an adhesive sheet having easy peelability due to heat and good storage stability. Another object associated with the present invention is to provide a method for peeling the above-mentioned adhesive sheet from an adherend.

[0016] Means for solving problems

[0017] According to the present specification, an adhesive sheet having an adhesive layer is provided. The adhesive layer comprises a polymer, a multifunctional monomer and a thermal polymerization initiator. In addition, the self-accelerating decomposition temperature (SADT) [°C] of the thermal polymerization initiator satisfies the following formula: SADT+10≥60. In addition, the peel force reduction rate A [%] of the adhesive sheet after heating is higher than 50% and lower than 99.9%.

[0018] The peel force reduction rate A after heating is calculated by the following formula:

[0019] A[%]=(1-F1 / F0)×100

[0020] (In the above formula, F1 is the peel strength after heating [N / 20mm] measured at 23°C after being attached to a glass plate and heated at 180°C for 1 hour, and F0 is the peel strength before heating of the glass plate [N / 20mm]).

[0021] The pressure-sensitive adhesive sheet having the above-mentioned structure has good heat-peelability and good storage stability.

[0022] In some embodiments, the polymer contains an ethylenically unsaturated group. According to the adhesive containing the polymer having the ethylenically unsaturated group, a more excellent heat-peelable property can be obtained. In addition, according to the adhesive containing the polymer having the ethylenically unsaturated group, the peeling force after heating can be better reduced under the condition of using a smaller amount of multifunctional monomers, and the desired heat-peelable property and heat-resistant peelable property can be ideally achieved.

[0023] In some embodiments, the adhesive layer includes an acrylic polymer as the polymer. The technology disclosed herein can be preferably implemented in an embodiment using an acrylic polymer.

[0024] In some embodiments, the adhesive layer includes a multifunctional acrylate monomer as the multifunctional monomer. The effect of the technology disclosed herein can be preferably achieved by using a multifunctional acrylate monomer as the multifunctional monomer. For example, by using an acrylic polymer and a multifunctional acrylate monomer in combination, the desired effect can be preferably achieved.

[0025] In some embodiments, the content of the polyfunctional monomer in the adhesive layer is less than 45 parts by weight based on 100 parts by weight of the polymer. By using the polyfunctional monomer in the above amount, the technology disclosed herein can be preferably implemented.

[0026] In some embodiments, the content of the thermal polymerization initiator in the adhesive layer is 0.1 parts by weight or more based on 100 parts by weight of the polymer. By containing a predetermined amount or more of the thermal polymerization initiator, the peeling force after heating can be preferably reduced.

[0027] In addition, according to the present specification, a method for peeling an adhesive sheet adhered to an adherend from the adherend is provided. The method includes: after subjecting an adherend to which any adhesive sheet disclosed herein is adhered to a heat treatment at a temperature higher than 150°C, the step of peeling the adhesive sheet from the adherend. The adhesive sheet disclosed herein has heat-resistant peelability (heat-resistant peelability), so it can be easily peeled from the adherend even after being exposed to heating exceeding 150°C. In addition, since the adhesive sheet has good storage stability, it can maintain heat-resistant peelability even when stored for a long time and regardless of the temperature conditions during storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] [ Figure 1 ] is a cross-sectional view schematically showing an example of a form of an adhesive sheet. DETAILED DESCRIPTION

[0029] The following describes a suitable embodiment of the present invention. Matters necessary for implementing the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of filing the application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field.

[0030] It should be noted that, in the following drawings, the same reference numerals are sometimes used to mark components and parts that play the same role for description, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are illustrated for the purpose of clearly describing the present invention, and do not necessarily accurately represent the size or reduction ratio of the product actually provided.

[0031] In this specification, the so-called "base polymer" of the adhesive refers to the main component of the rubber polymer contained in the adhesive. The so-called rubber polymer refers to a polymer that exhibits rubber elasticity in a temperature range near room temperature. In addition, in this specification, the so-called "main component" refers to a component contained in an amount exceeding 50% by weight unless otherwise specified.

[0032] In this specification, the term "acrylic polymer" refers to a polymer containing monomer units derived from a monomer having at least one (meth)acryloyl group in one molecule as monomer units constituting the polymer. The acrylic polymer in this specification is defined as a polymer containing monomer units derived from an acrylic monomer.

[0034] In addition, in this specification, the so-called "acrylic monomer" refers to a monomer having at least one (meth)acryloyl group in one molecule. Here, the so-called "(meth)acryloyl group" refers to both acryloyl and methacryloyl groups. Therefore, the concept of acrylic monomers mentioned here may include both monomers having an acryloyl group (acrylic monomer) and monomers having a methacryloyl group (methacrylic monomer). Similarly, in this specification, respectively, the so-called "(meth)acrylic acid" refers to both acrylic acid and methacrylic acid, and the so-called "(meth)acrylate" refers to both acrylate and methacrylate. The same is true for other similar terms.

[0035] In addition, in this specification, "weight" can be replaced by "mass". For example, "weight %" can be replaced by "mass %", and "weight parts" can be replaced by "mass parts".

[0036] <Adhesive composition>

[0037] (polymer)

[0038] In the technology disclosed herein, the type of adhesive is not particularly limited. The adhesive composition (and thus the adhesive (layer). Unless otherwise specified, the same below) used to form the adhesive may include one or more polymers of various rubber-like polymers such as acrylic polymers, rubber polymers (such as natural rubber, synthetic rubber, mixtures thereof, etc.), polyester polymers, urethane polymers, polyether polymers, silicone polymers, polyamide polymers, fluorine polymers, etc. that can be used in the field of adhesives. The above polymers are used as base polymers in the adhesive and can function as structural polymers of the molding adhesive. From the viewpoints of adhesive performance, cost, etc., it is preferred to use an adhesive composition containing an acrylic polymer or a rubber polymer as a base polymer. Among them, an adhesive composition (acrylic adhesive composition) using an acrylic polymer with excellent heat resistance as a base polymer is preferred.

[0039] Hereinafter, the acrylic pressure-sensitive adhesive composition and the pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer composed of the pressure-sensitive adhesive composition, that is, having an acrylic pressure-sensitive adhesive layer will be mainly described, but the pressure-sensitive adhesive composition disclosed herein is not intended to be limited to the acrylic pressure-sensitive adhesive composition.

[0040] (Acrylic polymer)

[0041] In some embodiments, as an acrylic polymer, an acrylic polymer in which more than 50% by weight of the monomer components constituting the polymer are acrylic monomers is used. It is appropriate that the proportion of acrylic monomers in the above-mentioned monomer components is 60% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 85% by weight or more, for example, it can be 90% by weight or more. The upper limit of the proportion of acrylic monomers in the monomer components constituting the acrylic polymer is 100% by weight. From the viewpoint of obtaining the effect of using non-acrylic monomers, the proportion of the above-mentioned acrylic monomers can be, for example, 98% by weight or less, 95% by weight or less, or 92% by weight or less. Acrylic monomers can be used alone or in combination of two or more.

[0042] In some embodiments, the monomer component includes an alkoxy-containing (meth)acrylate. According to the acrylic polymer containing an alkoxy-containing (meth)acrylate as a monomer component, for example, there is a tendency to easily obtain compatibility with the multifunctional monomer described later. The alkoxy-containing (meth)acrylate can be used alone or in combination of two or more.

[0043] Examples of (meth)acrylates containing an alkoxy group include alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; alkoxy (poly)alkylene glycol (meth)acrylates such as methoxydiethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethoxydipropylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, and ethoxypolypropylene glycol (meth)acrylate; and the like. Among them, alkoxyalkyl (meth)acrylates are preferred, and among them, alkoxyalkyl (meth)acrylates having an alkoxy group having 1 to 4 carbon atoms (eg, 1, 2, or 3 carbon atoms) are more preferred, and methoxyethyl (meth)acrylate is particularly preferred.

[0044] The content of the alkoxy-containing (meth)acrylate in the monomer component constituting the acrylic polymer is not particularly limited. From the viewpoint of effectively obtaining the effect brought about by the use of the alkoxy-containing (meth)acrylate, the content of the alkoxy-containing (meth)acrylate in the above-mentioned monomer component is usually about 1% by weight or more, for example, it can be 10% by weight or more, it can be 30% by weight or more, and it can also be 50% by weight or more. In some embodiments, from the viewpoint of adhesive properties such as adhesive strength and compatibility with multifunctional monomers, the content of the alkoxy-containing (meth)acrylate in the above-mentioned monomer component is, for example, more than 50% by weight, preferably 60% by weight or more, more preferably 70% by weight or more, and further preferably 80% by weight or more. The upper limit of the content of the alkoxy-containing (meth)acrylate in the above-mentioned monomer component is 100 wt% or less. For example, from the viewpoint of obtaining the effect of other copolymerizable monomers such as monomers containing functional groups, in some embodiments, the content of the alkoxy-containing (meth)acrylate is advantageously about 99 wt% or less, and can be 95 wt% or less, 93 wt% or less, or 90 wt% or less. In some other embodiments, the content of the alkoxy-containing (meth)acrylate can be about 80 wt% or less, 70 wt% or less, 65 wt% or less, or 60 wt% or less.

[0045] In some other embodiments, the monomer component constituting the acrylic polymer may be a component containing a linear alkyl (meth)acrylate having a linear or branched alkyl group with 1 to 20 carbon atoms at the ester terminal. Hereinafter, a linear alkyl (meth)acrylate having an alkyl group with X to Y carbon atoms at the ester terminal may be referred to as “C X-Y Alkyl (meth) acrylate". It should be noted that in the present specification, the term "chain" is used to include linear and branched chains. The above-mentioned chain alkyl (meth) acrylates can be used alone or in combination of two or more.

[0046] As C 1-20Specific non-limiting examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, Nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like.

[0047] Among these, it is preferred to use at least C 4-20 Alkyl (meth) acrylate, more preferably at least C 4-18 In some embodiments, as C 1-20 Alkyl (meth) acrylate, preferably C 4-8 Among them, it is more preferred to use C 4-8 Alkyl acrylate. 4-8 The alkyl (meth)acrylate can be used alone or in combination of two or more. 4-8 The use of alkyl (meth) acrylates tends to easily obtain good adhesive properties (adhesive strength, etc.). For example, as the above-mentioned monomer component, an acrylic polymer containing one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) is preferred, and an acrylic polymer containing at least 2EHA is particularly preferred. 1-20 In some other forms of alkyl (meth) acrylate, C 7-12 Alkyl (meth) acrylate. 7-12 The alkyl (meth)acrylate can be used alone or in combination of two or more. 7-12 Alkyl (meth) acrylate, preferably C 7-10 Alkyl acrylate, more preferably C 7-9 The alkyl acrylate is more preferably a C8 alkyl acrylate.

[0048] Among the monomer components constituting the acrylic polymer, 1-20The content of alkyl (meth) acrylate is not particularly limited. 1-20 From the viewpoint of the effect of using alkyl (meth)acrylate, C 1-20 The content of the alkyl (meth) acrylate is generally about 1% by weight or more, for example, 10% by weight or more, 30% by weight or more, or 50% by weight or more. In some embodiments, from the perspective of adhesive properties such as adhesive strength, the C 1-20 The content of the alkyl (meth)acrylate is, for example, more than 50% by weight, preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. 1-20 The upper limit of the content of the alkyl (meth) acrylate is 100 wt % or less. For example, from the perspective of obtaining the effect of other copolymerizable monomers such as monomers containing functional groups, in some embodiments, the C 1-20 The content of the alkyl (meth)acrylate is advantageously about 99 wt % or less, and may be 95 wt % or less, 93 wt % or less, or 90 wt % or less. 1-20 The content of alkyl (meth) acrylate can range from 1-20 The above C included in the alkyl (meth) acrylate 4-20 Alkyl (meth) acrylate, C 4-18 Alkyl (meth) acrylate, C 4-8 Alkyl (meth) acrylate, C 4-8 Alkyl acrylate, C 7-12 Alkyl (meth) acrylate, C 7-10 Alkyl acrylate, C 7-9 The range of each content of alkyl acrylate, C8 alkyl acrylate, BA, and 2EHA.

[0049] In some embodiments, the monomer components constituting the acrylic polymer preferably include other monomers other than the above-mentioned alkoxyalkyl (meth) acrylate and chain alkyl (meth) acrylate. Such other monomers may be monomers (copolymerizable monomers) that can be copolymerized with alkoxyalkyl (meth) acrylate and chain alkyl (meth) acrylate. As the above-mentioned other monomers, monomers having polar groups (e.g., carboxyl groups, hydroxyl groups, rings containing nitrogen atoms, etc.) may be preferably used. Monomers having polar groups may help introduce crosslinking points into acrylic polymers and improve the cohesive force of adhesives. Other monomers may be used alone or in combination of two or more.

[0050] Specific non-limiting examples of other monomers include the following monomers.

[0051] Carboxyl group-containing monomers: for example, acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and the like.

[0052] Monomers containing anhydride groups: for example, maleic anhydride, itaconic anhydride.

[0053] Monomers containing hydroxyl groups: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.

[0054] Monomers containing sulfonic acid groups or phosphoric acid groups: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, (meth)acrylate sulfopropyl ester, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethylacryloyl phosphate, etc.

[0055] Epoxy group-containing monomers: for example, epoxy group-containing acrylates such as glycidyl (meth)acrylate and 2-ethyl glycidyl (meth)acrylate ether, allyl glycidyl ether, and glycidyl (meth)acrylate ether.

[0056] Monomers containing cyano groups: for example, acrylonitrile, methacrylonitrile, etc.

[0057] Isocyanate group-containing monomer: for example, 2-isocyanateethyl (meth)acrylate, etc.

[0058] Monomers containing amide groups: for example, (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and the like N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and the like N-monoalkyl (meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinyl acetamide; Monomers having hydroxyl groups and amide groups, for example, N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, The monomers include N-hydroxyalkyl (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide and the like; monomers having an alkoxy group and an amide group, for example, N-alkoxyalkyl (meth)acrylamide, such as N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; and N,N-dimethylaminopropyl (meth)acrylamide, N-(meth)acryloyl morpholine, alkoxy diacetone (meth)acrylamide, vinyl formamide, vinyl acetamide and the like.

[0059] Monomers containing amino groups: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0060] Monomers having a ring containing a nitrogen atom: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylmorpholine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc. (for example, lactams such as N-vinyl-2-caprolactam).

[0061] Monomers having a succinimide skeleton include, for example, N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyhexamethylenesuccinimide.

[0062] Maleimides: for example, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.

[0063] Itaconimides: for example, N-methyl itaconimide, N-ethyl itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, N-lauryl itaconimide and the like.

[0064] Aminoalkyl (meth)acrylates: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0065] Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane.

[0066] Vinyl esters: for example, vinyl acetate, vinyl propionate, etc.

[0067] Vinyl ethers: For example, vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether.

[0068] Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc.

[0069] Olefins: for example, ethylene, butadiene, isoprene, isobutylene, etc.

[0070] (Meth)acrylates having an alicyclic hydrocarbon group: for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, adamantyl (meth)acrylate, and the like.

[0071] (Meth)acrylates having an aromatic hydrocarbon group: for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and the like.

[0072] In addition, (meth)acrylates containing heterocycles such as tetrahydrofurfuryl (meth)acrylate, (meth)acrylates containing halogen atoms such as (meth)acrylates containing vinyl chloride and fluorine atoms, (meth)acrylates containing silicon atoms such as silicone (meth)acrylates, and (meth)acrylates obtained from terpene compound derivative alcohols, etc.

[0073] When using such other monomers, its usage amount is not particularly limited, and it is appropriate to be set as more than 0.01 weight % of the overall monomer component. From the viewpoint of better exerting the use effect of other monomers, the usage amount of other monomers can be set as more than 0.1 weight % of the overall monomer component, and can be set as more than 0.5 weight %. In addition, from the viewpoint of easily obtaining the balanced property of adhesive properties, it is appropriate to set the usage amount of other monomers as less than 50 weight % of the overall monomer component, and preferably be set as less than 40 weight %.

[0074] In some embodiments, the monomer components constituting the acrylic polymer may include monomers having nitrogen atoms. By using monomers having nitrogen atoms, the cohesive force of the adhesive is increased, and the adhesive force can be ideally increased. Monomers having nitrogen atoms can be used alone or in combination of two or more. As a suitable example of a monomer having a nitrogen atom, a monomer having a ring containing a nitrogen atom can be cited. As monomers having a nitrogen atom and monomers having a ring containing a nitrogen atom, the monomers exemplified above can be used, for example, N-vinyl cyclic amide represented by general formula (1) can be used:

[0075] [Chemical formula 1]

[0076]

[0077] Here, in the general formula (1), R 1 is a divalent organic group, specifically -(CH2) n -. n is an integer of 2 to 7 (preferably 2, 3 or 4). Among them, N-vinyl-2-pyrrolidone (NVP) can be preferably used. Other suitable examples of monomers having nitrogen atoms include: N,N-dialkyl (meth)acrylamides such as (meth)acrylamide and N,N-dimethyl (meth)acrylamide; N-monoalkyl (meth)acrylamides such as N-isopropyl (meth)acrylamide; N-hydroxyalkyl (meth)acrylamides such as N-(2-hydroxyethyl)acrylamide (HEAA); N-acryloylmorpholine (ACMO); alkoxy diacetone (meth)acrylamide; vinyl formamide, vinyl acetamide; and the like. Among them, NVP, HEAA, and ACMO are more preferred.

[0078] The usage amount of the monomer with nitrogen atom (preferably the monomer with ring containing nitrogen atom) is not particularly limited, for example, it can be more than 1% by weight of the whole monomer component, or it can be more than 3% by weight. In some ways, the usage amount of the monomer with nitrogen atom in the above-mentioned monomer component is preferably more than 5% by weight, more preferably more than 7% by weight, and further preferably more than 9% by weight. In addition, it is appropriate to set the usage amount of the monomer with nitrogen atom to less than 40% by weight of the whole monomer component, which can be set to less than 35% by weight, can be set to less than 30% by weight, or can be set to less than 25% by weight. In some ways, the usage amount of the monomer with nitrogen atom can be set to less than 20% by weight of the whole monomer component, which can be set to less than 15% by weight, or can be set to less than 12% by weight.

[0079] In some embodiments, the monomer component may include a monomer containing a hydroxyl group. By using a monomer containing a hydroxyl group, the cohesion and crosslinking density of the adhesive can be adjusted, and the bonding strength can be improved. As a monomer containing a hydroxyl group, the monomers exemplified above can be used, for example, 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA) can be preferably used. The monomer containing a hydroxyl group can be used alone or in combination of two or more.

[0080] The amount used in the case of using a monomer containing a hydroxyl group is not particularly limited, for example, it can be more than 0.01% by weight of the entire monomer component, it can be more than 0.1% by weight, and it can also be more than 0.5% by weight. In some preferred embodiments, the amount of the monomer containing a hydroxyl group is more than 1% by weight of the entire monomer component, more preferably more than 2% by weight, and further preferably more than 3% by weight, for example, it can be more than 5% by weight. In addition, in some embodiments, it is appropriate to set the amount of the monomer containing a hydroxyl group to, for example, less than 40% by weight of the entire monomer component, preferably less than 30% by weight, more preferably less than 20% by weight, more preferably less than 10% by weight, and it can also be less than 7% by weight.

[0081] In some preferred embodiments, as monomer components of acrylic polymers, as monomers having polar groups (monomers containing polar groups), monomers having nitrogen atoms (e.g., monomers containing amide groups such as (meth)acrylamide, monomers containing rings containing nitrogen atoms such as NVP) and monomers containing hydroxyl groups (e.g., HEA, 4HBA) are used together. In this way, it is possible to achieve both adhesive force and cohesive force in a well-balanced manner. In the embodiment in which a monomer having nitrogen atoms and a monomer containing hydroxyl groups are used together, the amount of the monomer having nitrogen atoms is A N The amount of monomer containing hydroxyl group A OH Weight ratio (A N / A OH) is not particularly limited, and can be, for example, 0.1 or more, 0.5 or more, 1.0 or more, 1.2 or more, 1.5 or more, or 1.8 or more. N / A OH ) For example, it can be less than 10, less than 5, less than 3, or less than 2.5.

[0082] In some embodiments, the monomer component includes a monomer containing a carboxyl group. Suitable examples of monomers containing a carboxyl group include acrylic acid (AA) and methacrylic acid (MAA). Monomers containing a carboxyl group can be used alone or in combination of two or more. For example, AA and MAA can also be used in combination.

[0083] The usage amount of the monomer containing carboxyl can be, for example, more than 0.01 % by weight of the overall monomer component, can be more than 0.05 % by weight, can be more than 0.1 % by weight, can be more than 0.3 % by weight, and can also be more than 0.5 % by weight. The ratio of the above-mentioned monomer containing carboxyl can be, for example, less than 15 % by weight, can be less than 10 % by weight, can be less than 5 % by weight, can be less than 3 % by weight, can be less than 2 % by weight, and can also be less than 1 % by weight (for example, less than 1 % by weight).

[0084] In addition, when using an acrylic polymer with an ethylenically unsaturated group described later as a polymer, as other monomers, it is preferred to use a monomer with a functional group (functional group A) that can react with a functional group (functional group B) of a compound with an ethylenically unsaturated group described later. In this manner, the type of other monomers is determined according to the type of the above-mentioned compound. As other monomers with functional group A, for example, preferably a monomer containing a carboxyl group, a monomer containing an epoxy group, a monomer containing a hydroxyl group, a monomer containing an isocyanate group, and a monomer containing a hydroxyl group are particularly preferred. By using a monomer containing a hydroxyl group as other monomers, the acrylic polymer has a hydroxyl group. In contrast, as a compound with an ethylenically unsaturated group, for example, by using a monomer containing an isocyanate group, the hydroxyl group of the above-mentioned acrylic polymer reacts with the isocyanate group of the above-mentioned compound, and the ethylenically unsaturated group derived from the above-mentioned compound is introduced into the acrylic polymer.

[0085] In addition, when other monomers are used for the purpose of reacting with a compound having an ethylenically unsaturated group, from the viewpoint of adhesive properties such as thermosetting and cohesive force of the adhesive, it is appropriate that the amount of the other monomers (preferably monomers containing hydroxyl groups) is set to about 1 mol% or more of the total monomer components, preferably about 5 mol% or more, more preferably about 10 mol% or more, and further preferably about 15 mol% or more (for example, about 18 mol% or more). In addition, from the viewpoint of maintaining adhesive properties such as adhesive force well, it is appropriate that the amount of the other monomers is set to about 40 mol% or less of the total monomer components, preferably about 30 mol% or less, more preferably about 25 mol% or less, and for example, it can also be about 22 mol% or less.

[0086] In the acrylic polymer, as other monomer components, a multifunctional monomer having a polymerizable functional group (typically a free radical polymerizable functional group) having at least 2 (meth)acryloyl groups, vinyl groups, etc. with unsaturated double bonds can be included. As a monomer component, by using a multifunctional monomer, the cohesive force of the adhesive can be improved. The multifunctional monomer can be used as a crosslinking agent. As a multifunctional monomer, there is no particular limitation, for example, a suitable substance among the substances exemplified as the multifunctional monomer contained in the adhesive composition described later can be used alone or in combination of two or more.

[0087] The usage amount of the multifunctional monomer is not particularly limited, and can be appropriately set in a manner that achieves the purpose of use of the multifunctional monomer. The usage amount of the multifunctional monomer can be set to less than about 3 wt % of the above-mentioned monomer component, preferably less than about 2 wt %, more preferably less than about 1 wt % (e.g., less than about 0.5 wt %). The lower limit of the usage amount when using a multifunctional monomer is greater than 0 wt %, and is not particularly limited. Usually, by setting the usage amount of the multifunctional monomer to more than about 0.001 wt % of the monomer component (e.g., more than about 0.01 wt %), the use effect of the multifunctional monomer can be appropriately exerted.

[0088] The method for obtaining the acrylic polymer is not particularly limited, and various polymerization methods known as the synthesis methods of acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization, can be appropriately adopted. For example, solution polymerization can be preferably adopted. As a monomer supply method when performing solution polymerization, a one-time feeding method of supplying all monomer raw materials at one time, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be set to about 20°C to 170°C (typically about 40°C to 140°C).

[0089] The solvent (polymerization solvent) used in solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any solvent selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; etc., or a mixed solvent of two or more can be used.

[0090] The initiator used in the polymerization can be appropriately selected from conventionally known polymerization initiators according to the type of polymerization method. For example, although not particularly limited, azo polymerization initiators, peroxide polymerization initiators, redox polymerization initiators based on a combination of peroxide and a reducing agent, substituted ethane polymerization initiators, etc. can be used. As the polymerization initiator, for example, one or more of the substances exemplified as thermal polymerization initiators added to the adhesive composition described later can be selected and used.

[0091] The amount of the polymerization initiator used can be set to a normal amount corresponding to the polymerization method, polymerization mode, etc., and is not particularly limited. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example, about 0.01 to 1 part by weight) of the polymerization initiator can be used relative to 100 parts by weight of all monomer components of the polymerization object.

[0092] The molecular weight of the polymer (for example, an acrylic polymer) is not particularly limited and can be set within an appropriate range depending on the required performance, etc. The weight average molecular weight (Mw) of the above polymer is about 1×10 4 The above is suitable, for example, it can be about 10×10 4 By using a polymer having an Mw of a predetermined value or more, cohesive force and adhesive force can be achieved in a well-balanced manner. In some embodiments, the Mw may be 20×10 4 Above, it can be 30×10 4 Above, it can be about 40×10 4 Above, it can be about 50×10 4 For example, it can be about 55×10 4 The upper limit of the Mw of the above polymer is not particularly limited, and can be, for example, about 1000×10 4 Below, it can also be about 100×10 4Here, Mw refers to a value obtained by gel permeation chromatography (GPC) in terms of standard polystyrene. As a GPC apparatus, for example, a model "HLC-8320GPC" (chromatographic column: TSKgelGMH-H(S), manufactured by Tosoh Corporation) can be used.

[0093] (Polymer having ethylenically unsaturated groups)

[0094] In some ways, as a polymer, it is preferred to use a polymer (the amount of ethylenically unsaturated groups is less than 0.01mmol / g) that does not substantially have ethylenically unsaturated groups such as acryloyl, methacryloyl, vinyl, and allyl. In some other ways, a polymer with ethylenically unsaturated groups can be used. According to the adhesive comprising a polymer with ethylenically unsaturated groups, in addition to the thermal curing brought by the multifunctional monomer described later, by reacting the ethylenically unsaturated groups possessed by the polymer when heated, the adhesive is thermally cured, and a more excellent heating easy peelability can be obtained. In addition, according to the adhesive comprising a polymer with ethylenically unsaturated groups, the reduction rate of the peeling force after heating can be improved with the use of a smaller amount of multifunctional monomers, and the desired heating easy peelability and heat-resistant easy peelability can be achieved. As a polymer with ethylenically unsaturated groups, for example, a polymer with ethylenically unsaturated groups in the side chain can be used. As a monomer component of a polymer with ethylenically unsaturated groups, one or more of the monomer components exemplified as the above-mentioned polymer can be used within the range of the above-mentioned content.

[0095] The amount of the ethylenically unsaturated group in the polymer with ethylenically unsaturated groups is not particularly limited. From the viewpoints of thermosetting properties, it is appropriate to set it to 0.01mmol (hereinafter, also referred to as mmol / g) or more relative to each 1g of polymer, and it can be more than 0.1mmol / g, or more than 0.5mmol / g. In addition, it is appropriate to set the amount of the ethylenically unsaturated group in the above-mentioned polymer to less than 10.0mmol / g, and it can be less than 5.0mmol / g, and it can be less than 3.0mmol / g, and it can be less than 2.5mmol / g, and it can be less than 2.0mmol / g.

[0096] The amount of the ethylenically unsaturated group in the polymer is measured by the following method, for example, when the ethylenically unsaturated group is a (meth)acryloyl group.

[0097] First, 0.25 mg of the polymer to be measured is dissolved in 50 mL of THF (tetrahydrofuran), and 15 mL of methanol is further added to obtain a solution. Then, 10 mL of 4N sodium hydroxide aqueous solution is added to the above solution to obtain a mixed solution. Then, the above mixed solution is stirred at a liquid temperature of 40°C for 2 hours. Furthermore, 10.2 mL of 4N methanesulfonic acid solution is added to the above mixed solution and stirred. 5 mL of desalted water is added thereto, followed by 2 mL of methanol to prepare a measurement solution.

[0098] The (meth)acrylic acid content in the measurement solution was measured by HPLC (High Performance Liquid Chromatography) method (absolute standard curve method), and the ethylenically unsaturated group content was calculated.

[0099] (HPLC measurement conditions)

[0100] Chromatographic column: Synergi 4μPolar-RP 80A (4.6 mm × 250 mm) manufactured by Phenomenex

[0101] Column temperature: 40°C

[0102] Flow rate: 1.0mL / min

[0103] Detector wavelength: 210nm

[0104] Eluent: THF (for HPLC) 55 / buffer (containing 0.2% phosphoric acid, 0.2% triethylamine) 45

[0105] Aqueous solution injection volume: 5μL

[0106] As a method for measuring the content of other ethylenically unsaturated groups other than (meth)acryloyl groups, there can be mentioned a method for measuring the bromine value in accordance with JIS K2605: 1996. In this measurement method, the content of other ethylenically unsaturated groups other than (meth)acryloyl groups can be determined by converting the number of grams of bromine (Br2) added to 100 g of the polymer to be measured into the number of moles of bromine (Br2) added to 1 g of the polymer.

[0107] The method of introducing ethylenically unsaturated groups into polymers is not particularly limited. For example, it is possible to preferably adopt a method in which a compound having a functional group (functional group B) and an ethylenically unsaturated group that can react with a functional group (functional group A) introduced into an acrylic polymer by copolymerization and reacts in a manner that the ethylenically unsaturated group does not disappear (typically a condensation reaction or an addition reaction). Examples of combinations of functional group A and functional group B include a combination of a carboxyl group and an epoxy group, a combination of a carboxyl group and an aziridine group, a combination of a hydroxyl group and an isocyanate group, and the like. Among them, from the viewpoint of reaction tracking, a combination of a hydroxyl group and an isocyanate group is preferred. From the viewpoints of polymer design, it is particularly preferred that the acrylic polymer has a hydroxyl group and the above-mentioned compound has an isocyanate group.

[0108] The compound having an ethylenically unsaturated group may have a functional group B that can react with the functional group A as described above. As a suitable example of such a compound, for example, a monomer containing an isocyanate group (a compound containing an isocyanate group) exemplified as other monomers that can be used for the polymerization of an acrylic polymer can be cited. Among them, 2-(meth)acryloyloxyethyl isocyanate is more preferred. The acrylic polymer having an ethylenically unsaturated group can be obtained by reacting the isocyanate group of the compound containing an isocyanate group having an ethylenically unsaturated group with the hydroxyl group of the acrylic polymer to form a bond (specifically, a carbamate bond).

[0109] The amount of the compound having an ethylenically unsaturated group (e.g., a monomer containing an isocyanate group) added is not particularly limited, and can be 1:1 molar amount (M) of the functional group A in the polymer. A ) and the molar ratio (M B ) molar ratio (M A / M B ) is set so as to be in the range of about 0.5 to 2 (for example, 1 to 1.5).

[0110] In the method of using a polymer with an ethylenically unsaturated group as a polymer, the content of the polymer with an ethylenically unsaturated group in the adhesive composition is not particularly limited. In some methods, the amount of the polymer with an ethylenically unsaturated group in the non-volatile component (solid content) of the adhesive composition can be about 50% by weight or less (for example, less than 50% by weight), can be less than 30% by weight, can be less than 10% by weight, or can be less than 1% by weight. The technology disclosed herein can be implemented using an adhesive composition that does not substantially contain a polymer with an ethylenically unsaturated group. In some other methods, from the perspective of obtaining excellent heating and easy peelability, it is appropriate to set the amount of the polymer with an ethylenically unsaturated group to about 10% by weight or more of the polymer (specifically, the base polymer) contained in the adhesive composition as a whole, which can be about 50% by weight or more (for example, more than 50% by weight), can be more than 70% by weight, can be more than 90% by weight, can be more than 95% by weight, or can be 99 to 100% by weight. In some methods, the base polymer contained in the adhesive composition can be substantially formed by a polymer with an ethylenically unsaturated group.

[0111] (Multifunctional monomer)

[0112] In the adhesive composition disclosed herein, in addition to the above-mentioned polymer, a multifunctional monomer is also contained. By including a multifunctional monomer in the adhesive composition, the multifunctional monomer is contained in the adhesive (layer) in a state before reaction (unreacted). Thus, after the adhesive is formed, the multifunctional monomer contained in the adhesive reacts with the thermal polymerization initiator described later when heated at high temperature, so that the bonding force is reduced or the rise of the peeling force is suppressed, and easy peeling by heating can be achieved. By including a multifunctional monomer, a thermosetting adhesive having heat-resistant easy peeling after heat treatment can be formed. More specifically, usually, when being attached to an adherend, for example, when heated at high temperature, the adhesive will be adsorbed on the surface of the adherend. Therefore, the adhesive strength of the adhesive to the adherend is enhanced, and heavy peeling will occur. According to the technology disclosed herein, by including a multifunctional monomer of more than a specified amount together with a thermal polymerization initiator in the adhesive, the reaction (free radical polymerization reaction) of the multifunctional monomer and the thermal polymerization initiator is rapidly carried out when heated, and the adhesive curing can be carried out before the adsorption of the adhesive to the adherend. Thus, the adhesive strength to the adherend can be reduced. Furthermore, even if the heating is continued, the adhesive strength of the adhesive to the adherend will not increase, but will be maintained within a specified range, so the adhesive can exhibit excellent heating and easy peeling properties. It should be noted that the technology disclosed herein is not limited to the above investigation. The multifunctional monomer can be used alone or in combination of two or more.

[0113] It should be noted that in this specification, the so-called multifunctional monomer refers to a polymerizable compound having more than two ethylenically unsaturated groups in one molecule, and also includes substances called oligomers. The above-mentioned ethylenically unsaturated groups function as polymerizable functional groups (typically free radical polymerizable functional groups). Examples of ethylenically unsaturated groups possessed by multifunctional monomers include acryloyl, methacryloyl, vinyl and allyl groups, but are not limited to these. Suitable examples of ethylenically unsaturated groups include acryloyl and methacryloyl. Among them, acryloyl is preferred. Hereinafter, compounds having more than two acryloyl and / or methacryloyl groups are sometimes referred to as multifunctional acrylic monomers. In addition, compounds having more than two vinyl groups are sometimes referred to as multifunctional vinyl monomers.

[0114] The number of ethylenically unsaturated groups contained in one molecule of a multifunctional monomer is more than 3, preferably more than 4, more preferably more than 5, and may be more than 6. The more ethylenically unsaturated groups there are in a multifunctional monomer, the better the curability during heating, and the easier it is to obtain a tendency to be easily peeled by heating. In addition, by using a multifunctional monomer with more ethylenically unsaturated groups (functional groups), it is possible to obtain easy peeling by heating with a relatively small amount of use. This reduces the amount of released gas from the multifunctional monomer, which is beneficial. The upper limit of the number of ethylenically unsaturated groups in one molecule of a multifunctional monomer is not limited to a specific range, for example, it may be less than 50, may be less than 40, may be less than 30, may be less than 20, or may be less than 15. In some embodiments, the number of ethylenically unsaturated groups in one molecule of a multifunctional monomer may be, for example, less than 10, may be less than 8, may be less than 6, or may be less than 5. The polyfunctional monomer having the above number of ethylenically unsaturated groups tends to achieve both good adhesiveness and heat-peelability, and also tends to be excellent in storage stability.

[0115] As the multifunctional monomer, various multifunctional acrylate monomers and multifunctional vinyl monomers having 2 or more ethylenically unsaturated groups can be used. Among them, multifunctional acrylate monomers can be preferably used. Although not particularly limited, multifunctional acrylate monomers tend to exhibit desired properties with good compatibility when used in combination with acrylic polymers. Multifunctional acrylate monomers and multifunctional vinyl monomers can be used alone or in combination of two or more.

[0116] Examples of the polyfunctional monomer include 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, allyl (meth)acrylate, alkylene oxide-modified bisphenol A di(meth)acrylate, alkylene oxide-modified neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, vinyl (meth)acrylate, diethylene glycol di(meth)acrylate, Bifunctional monomers such as alkenylbenzene; trifunctional monomers such as trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, glycerol propoxy triacrylate, tetramethylolmethane tri(meth)acrylate, and pentaerythritol tri(meth)acrylate; quadrifunctional monomers such as pentaerythritol alkoxy tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate; pentafunctional monomers such as sorbitol penta(meth)acrylate and dipentaerythritol penta(meth)acrylate; hexafunctional monomers such as dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, alkylene oxide-modified hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate; and epoxy acrylates, polyester acrylates, and urethane acrylates having two or more functionalities. Among them, preferred examples include 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Among them, dipentaerythritol hexa(meth)acrylate is particularly preferred.

[0117] Although not particularly limited, it is appropriate to use a multifunctional monomer with a molecular weight of 100 or more as a multifunctional monomer. In some preferred embodiments, the molecular weight of the multifunctional monomer can be, for example, 150 or more, 250 or more, 300 or more, 350 or more, 400 or more, 450 or more, or 500 or more. In addition, the molecular weight of the multifunctional monomer is generally about 100,000 or less, for example, about 10,000 or less (for example, less than 10,000) is appropriate, preferably 5,000 or less (for example, less than 5,000), 1,500 or less, 1,000 or less (for example, less than 1,000), 800 or less, or 600 or less. The use of a multifunctional monomer with a molecular weight in the above range is advantageous, for example, in terms of the preparation and coating properties of the adhesive composition. It should be noted that the above molecular weight is a molecular weight calculated based on the manufacturer's nominal value or molecular structure. Regarding the polyfunctional monomer having a molecular weight equal to or greater than a predetermined value, the value of the weight average molecular weight (Mw) in terms of standard polystyrene obtained by GPC may be adopted.

[0118] In some preferred embodiments, as a multifunctional monomer, a multifunctional monomer having a weight loss rate of 1% or less (specifically, 1.0% or less) when reaching 180°C in TGA (thermogravimetric analysis) under a heating condition of 10°C / min is used. By using a heat-resistant multifunctional monomer having the above-mentioned 180°C heating weight loss rate of 1% or less (hereinafter, also referred to as a "heat-resistant multifunctional monomer"), the adhesive layer has heat-resistant peelability based on the use of the multifunctional monomer, and the generation of released gas during heating is suppressed. By using the above-mentioned heat-resistant multifunctional monomer, it is possible to achieve both heat-resistant peelability and reduced released gas. From the viewpoint of reduced released gas, in some preferred embodiments, the 180°C heating weight loss rate of the heat-resistant multifunctional monomer is 0.9% or less, more preferably 0.8% or less, further preferably 0.7% or less, particularly preferably 0.6% or less, and may also be 0.5% or less. The lower limit of the weight loss rate of the heat-resistant multifunctional monomer at 180°C heating is theoretically 0%, and can be 0.1% or more, 0.2% or more, or 0.3% or more in practice. As the heat-resistant multifunctional monomer, trimethylolpropane triacrylate (TMPTA, weight loss rate is 1% at 180°C) and dipentaerythritol hexaacrylate (DPHA, weight loss rate is 0.5% at 180°C) are preferably used. The heat-resistant multifunctional monomer can be used alone or in combination of two or more.

[0119] The 180° C. heating weight loss rate of the polyfunctional monomer can be specifically measured using a differential thermal analyzer (manufactured by TA Instruments, trade name “Discovery TGA”) under measurement conditions of a temperature increase of 10° C. / min, an air atmosphere, and a flow rate of 25 mL / min.

[0120] The content of the heat-resistant multifunctional monomer in the adhesive composition is not particularly limited. In some embodiments, the content of the heat-resistant multifunctional monomer in the adhesive composition is preferably 30 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. Suitably an acrylic polymer) contained in the adhesive composition. The appropriate amount of the heat-resistant multifunctional monomer may vary according to its molecular weight, the number of functional groups, etc. In some preferred embodiments, from the perspective of easy peelability by heating, it is appropriate to set the amount of the heat-resistant multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer to be 50 parts by weight or more, preferably 60 parts by weight or more, more preferably 70 parts by weight or more, further preferably 80 parts by weight or more, particularly preferably 90 parts by weight or more, and may also be 100 parts by weight or more. In some other embodiments (not particularly limited, such as the method of using a polymer having an ethylenically unsaturated group), the content of the heat-resistant multifunctional monomer relative to 100 parts by weight of the polymer contained in the adhesive composition can be about 1 part by weight or more, or 3 parts by weight or more. In some preferred embodiments, from the viewpoint of easy peelability by heating, the content of the heat-resistant multifunctional monomer is 5 parts by weight or more, can be 7 parts by weight or more, can be 8 parts by weight or more, can be 9 parts by weight or more, more preferably 10 parts by weight or more (for example, more than 10 parts by weight), more preferably 15 parts by weight or more, further preferably 20 parts by weight or more, and further preferably 25 parts by weight or more. The upper limit of the content of the heat-resistant multifunctional monomer in the adhesive composition is not particularly limited and can be set in a manner to achieve the desired adhesive properties. In some embodiments, from the viewpoint of compatibility with a polymer (specifically a base polymer. For example, an acrylic polymer), it is appropriate to set the amount of the heat-resistant multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer to be about 200 parts by weight or less, preferably 160 parts by weight or less, more preferably 150 parts by weight or less, further preferably 140 parts by weight or less, can be 120 parts by weight or less, and can also be 90 parts by weight or less. In some other preferred embodiments, the amount of the heat-resistant multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer can be 70 parts by weight or less, 50 parts by weight or less (e.g., less than 50 parts by weight), 45 parts by weight or less (e.g., less than 45 parts by weight), 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, 25 parts by weight or less, 20 parts by weight or less (e.g., less than 20 parts by weight), 18 parts by weight or less, 15 parts by weight or less, or 12 parts by weight or less. The amount of the heat-resistant multifunctional monomer limited in this way can be preferably adopted in the mode of using a polymer with an ethylenically unsaturated group. In addition, regarding the use of limiting the heat-resistant multifunctional monomer, this is also preferred from the viewpoint of preventing or suppressing the contamination of the adherend after the adhesive is peeled off.

[0121] The content of the multifunctional monomer in the adhesive composition is not particularly limited. In some embodiments, the content of the multifunctional monomer in the adhesive composition is 50 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. Suitably, an acrylic polymer) contained in the adhesive composition. By making the adhesive composition and then the adhesive contain a sufficient amount of multifunctional monomers, when heated, the multifunctional monomers contained in the adhesive react rapidly, and the adhesive is thermally cured, thereby achieving easy peeling by heating. The appropriate amount of the multifunctional monomer may vary according to its molecular weight, the number of functional groups, etc., but generally, from the viewpoint of easy peeling by heating, the amount of the multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer is preferably 60 parts by weight or more, more preferably 70 parts by weight or more, further preferably 80 parts by weight or more, particularly preferably 90 parts by weight or more, and may also be 100 parts by weight or more. In some other methods (not particularly limited, such as the method of using a polymer having an ethylenically unsaturated group), the content of the multifunctional monomer can be about 1 part by weight or more, or 3 parts by weight or more relative to 100 parts by weight of the polymer contained in the adhesive composition. In some preferred embodiments, from the perspective of easy peelability by heating, the content of the multifunctional monomer is 5 parts by weight or more, 7 parts by weight or more, 8 parts by weight or more, 9 parts by weight or more, more preferably 10 parts by weight or more (for example, more than 10 parts by weight), more preferably 15 parts by weight or more, further preferably 20 parts by weight or more, and further preferably 25 parts by weight or more. The upper limit of the content of the multifunctional monomer in the adhesive composition is not particularly limited and can be set in a manner to achieve the desired adhesive properties. In some embodiments, from the perspective of compatibility with the polymer (specifically, the base polymer, such as an acrylic polymer), it is appropriate to set the amount of the multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer to be about 200 parts by weight or less, preferably 160 parts by weight or less, more preferably 150 parts by weight or less, and further preferably 140 parts by weight or less, and can be 120 parts by weight or less, or 90 parts by weight or less. In some other preferred embodiments, the amount of the multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer can be 70 parts by weight or less, can be 50 parts by weight or less (e.g., less than 50 parts by weight), can be 45 parts by weight or less (e.g., less than 45 parts by weight), can be 40 parts by weight or less, can be 35 parts by weight or less, can be 30 parts by weight or less, can be 25 parts by weight or less, can be 20 parts by weight or less (e.g., less than 20 parts by weight), can be 18 parts by weight or less, can be 15 parts by weight or less, and can be 12 parts by weight or less. The use amount of the polyfunctional monomer limited in this manner can be preferably adopted in the embodiment using the polymer having an ethylenically unsaturated group.In addition, limiting the amount of the polyfunctional monomer used is also preferred from the viewpoint of preventing or suppressing contamination of the adherend after the PSA is peeled off.

[0122] (Thermal polymerization initiator)

[0123] The adhesive composition disclosed herein contains a thermal polymerization initiator in addition to the above-mentioned polymer and multifunctional monomer. Here, the so-called thermal polymerization initiator refers to a polymerization initiator that generates free radicals by heating. By including a thermal polymerization initiator in the adhesive composition, the thermal polymerization initiator is contained in the adhesive (layer) in a pre-reaction (unreacted) state. Thus, after the adhesive is formed, the thermal polymerization initiator contained in the adhesive reacts with the multifunctional monomer when heated at high temperature, so that the adhesive force is reduced or the increase in the adhesive force is suppressed, and easy peelability by heating can be achieved. By including a thermal polymerization initiator, a thermosetting adhesive that is also heat-resistant and easy to peel after heat treatment can be formed. The thermal polymerization initiator can be used alone or in combination of two or more.

[0124] In some embodiments, as a thermal polymerization initiator contained in the adhesive composition, a thermal polymerization initiator having a self-accelerating decomposition temperature (SADT) [°C] that satisfies the following formula is used: SADT+10≥60. Here, the SADT of the so-called thermal polymerization initiator is defined as the lowest temperature that causes heat generation of 6°C or more or self-accelerating decomposition within 7 days when placed in a certain amount of a container. SADT represents the ambient temperature at the boundary of whether the thermal polymerization initiator causes decomposition. Based on the fact that the maximum temperature to which the adhesive is exposed during storage is 60°C, the inventors of the present application have experimentally confirmed that if the thermal polymerization initiator has a SADT of -10°C or a temperature higher than the above-mentioned maximum temperature during storage, the self-decomposition of the thermal polymerization initiator in the adhesive can be suppressed, and storage stability that can maintain good heat-peelable properties after storage can be obtained. It is believed that this is because it is more difficult to conduct heat in the adhesive (in the solid) compared to the case of a single thermal polymerization initiator. Based on this discovery, according to an adhesive designed using a thermal polymerization initiator having a SADT satisfying the above formula (hereinafter also referred to as a high SADT initiator), even if the adhesive is exposed to a temperature of about 60°C before use, the decomposition of the thermal polymerization initiator in the adhesive is suppressed, and the adhesive can maintain the desired heat-peelable property. According to an adhesive containing a thermal polymerization initiator containing a high SADT initiator, even in the case of long-term storage, temperature changes during storage, etc., the storage stability is also very good, and good heat-peelable property can be maintained after storage. It should be noted that in this specification, the SADT as a thermal polymerization initiator adopts the nominal value recorded in the manufacturer's catalog, etc.

[0125] As a high SADT initiator, for example, a thermal polymerization initiator having a SADT of 50°C or higher can be selected and used from various thermal polymerization initiators such as peroxide-based polymerization initiators, azo-based polymerization initiators, redox-based polymerization initiators based on a combination of peroxide and a reducing agent, and substituted ethane-based polymerization initiators. Among them, it is preferred to use peroxide-based and azo-based high SADT initiators, and it is more preferred to use peroxide-based high SADT initiators. By using a peroxide-based initiator as a thermal polymerization initiator, the desired reduction rate of peel force after heating can be ideally achieved. The high SADT initiator can be used alone or in combination of two or more.

[0126] As the peroxide-based high SADT initiator, for example, an organic peroxide having a SADT of 50° C. or higher can be selected from organic peroxides such as diacyl peroxides, peroxyesters, peroxydicarbonates, monoperoxycarbonates, peroxyketals, dialkyl peroxides, hydroperoxides, and ketone peroxides and used. Specific non-limiting examples of peroxide-based high SADT initiators include dibenzoyl peroxide (BPO) (SADT: 75° C.), 1,1-di(tert-hexylperoxy)cyclohexane (SADT: 65° C.), 1,1-bis(tert-butylperoxy)cyclohexane (SADT: 60° C.), cumene hydroperoxide (SADT: 80° C.), 1,3-bis(tert-butylperoxy)m-isopropylbenzene (SADT: 85° C.), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (SADT: 90° C.), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3 (SADT: 90° C.), diisopropylbenzene hydroperoxide (SADT: 80° C.), and tert-butyl peroxybenzoate (SADT: 65° C.). A suitable example of a peroxide-based high SADT initiator includes BPO. The peroxide-based high SADT initiator can be used alone or in combination of two or more.

[0127] Examples of commercially available peroxide-based high SADT initiators include “PERHEXA HC”, “PERHEXA C” series, “PERCUMYL H-80”, “PERCUMYL P”, “PERHEXA 25B” series, “PERBUTYL P” series, “PERHEXYNE 25B” series, “NYPER BW”, “NYPER NS”, and “PERBUTYL Z” manufactured by NOF Corporation.

[0128] As the azo high SADT initiator, for example, a compound having a SADT of 50° C. or higher can be selected and used from azonitrile compounds, azoamide compounds, azoester compounds, alkylazo compounds, azoamidine compounds, azoimidazoline compounds, and polymer azo compounds. Non-limiting examples of the azo high SADT initiator include 2,2'-azobisisobutyronitrile (AIBN), 1,1'-azobis(cyclohexane-1-carbonitrile), 4,4-azobis(4-cyanovaleric acid), 2,2'-azobis(N-butyl-2-methylpropionamide), and 2,2'-azobis(2,4,4-trimethylpentane). The azo high SADT initiator can be used alone or in combination of two or more.

[0129] In addition, in some embodiments, at least an azo polymerization initiator is used as a thermal polymerization initiator. According to the adhesive containing an azo polymerization initiator as a thermal polymerization initiator, even in the case of long-term storage, temperature changes during storage, etc., the desired heat-peelable property can be maintained after storage. By using an azo polymerization initiator as a thermal polymerization initiator, an adhesive with good storage stability can be formed. As a reason for this, it is believed that compared with other types of polymerization initiators, the azo polymerization initiator has good thermal stability in an adhesive containing a polymer and a multifunctional monomer, but the technology disclosed herein is not limited to the above-mentioned investigation. In addition, when an azo polymerization initiator is used as a thermal polymerization initiator, there is a tendency for the amount of released gas from the adhesive to decrease. Azo polymerization initiators can be used alone or in combination of two or more.

[0130] The azo polymerization initiator used in the technology disclosed herein is not particularly limited, and any of azonitrile compounds, azoamide compounds, azoester compounds, alkylazo compounds, azoamidine compounds, azoimidazoline compounds, and polymer azo compounds can be used. Non-limiting specific examples of azo polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 1,1'-azobis(cyclohexane-1-carbonitrile), 4,4-azobis(4-cyanovaleric acid), 2,2'-azobis(N-butyl-2-methylpropionamide), and 2,2'-azobis(2,4,4-trimethylpentane).

[0131] Although not particularly limited, as the above-mentioned azo-based polymerization initiator, a polymerization initiator having a 10-hour half-life temperature of, for example, 50°C or more can be preferably used. Here, the so-called 10-hour half-life temperature of the polymerization initiator refers to the temperature at which the concentration of the initiator becomes half after 10 hours, and is used as an index to indicate the decomposition rate of the polymerization initiator and the thermal decomposition property (free radical generation property) at a specified temperature. In this specification, the nominal value recorded in the manufacturer's catalog, etc. is used as the 10-hour half-life temperature of the polymerization initiator. In the case where there is no manufacturer's nominal value, the value measured using an appropriate solvent (such as toluene) can be used. Although it is believed that the thermal decomposition property of the thermal polymerization initiator in the adhesive is different from that in the solvent, the thermal polymerization initiator with a high 10-hour half-life temperature tends to have excellent heat resistance and storage stability. From the above viewpoints, the 10-hour half-life temperature of the azo polymerization initiator is preferably 55°C or higher, more preferably 60°C or higher, further preferably 65°C or higher, particularly preferably 70°C or higher, 80°C or higher, 90°C or higher, or 100°C or higher (e.g., more than 100°C). The upper limit of the 10-hour half-life temperature of the azo polymerization initiator is, for example, 150°C or lower, and 120°C or lower is appropriate. In some preferred embodiments, an azo polymerization initiator having a 10-hour half-life temperature of, for example, 100°C or lower (e.g., lower than 100°C, 95°C or lower, or 90°C or lower) can be used.

[0132] In some embodiments, the content of the azo polymerization initiator in the adhesive composition is 0.1 parts by weight or more (0.10 parts by weight or more) relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive composition. By making the adhesive composition and then making the adhesive contain the above-mentioned amount of azo polymerization initiator, the azo polymerization initiator and the multifunctional monomer are fully contacted in the adhesive, so that the reaction of the two can proceed rapidly. Thus, an adhesive with good heat-peelability can be formed. In addition, the adhesive can have good storage stability by containing an azo polymerization initiator. From the above viewpoint, the amount of the azo polymerization initiator relative to 100 parts by weight of the above-mentioned polymer is preferably 0.15 parts by weight or more, more preferably 0.20 parts by weight or more, and further preferably 0.25 parts by weight or more, can be 0.30 parts by weight or more, can be 0.35 parts by weight or more, can be 0.40 parts by weight or more, can be 0.45 parts by weight or more, and can also be 0.50 parts by weight or more. The upper limit of the content of the azo polymerization initiator in the adhesive composition is not particularly limited, and can be appropriately set in a manner that does not damage the adhesive properties such as adhesive strength and storage stability. In some embodiments, the amount of the azo polymerization initiator relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) is, for example, about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), can be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), can be less than 0.8 parts by weight, and can also be less than 0.6 parts by weight (for example, less than 0.4 parts by weight).

[0133] The content of the azo polymerization initiator in the adhesive composition can also be determined by the relative relationship with the multifunctional monomer contained in the adhesive composition. In some embodiments, from the viewpoint of the probability of contact with the multifunctional monomer, it is appropriate to set the amount of the azo polymerization initiator relative to 100 parts by weight of the multifunctional monomer to be 0.1 parts by weight or more (0.10 parts by weight or more), preferably 0.15 parts by weight or more, more preferably 0.20 parts by weight or more, further preferably 0.25 parts by weight or more, can be 0.30 parts by weight or more, can be 0.35 parts by weight or more, can be 0.40 parts by weight or more, can be 0.45 parts by weight or more, and can also be 0.50 parts by weight or more. In some embodiments, the amount of the azo polymerization initiator relative to 100 parts by weight of the multifunctional monomer is, for example, appropriately about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), may be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), may be less than 0.8 parts by weight, or may be less than 0.6 parts by weight (for example, less than 0.4 parts by weight).

[0134] In the method of using an azo polymerization initiator as a thermal polymerization initiator, the adhesive composition, and then the adhesive (layer) only contains an azo polymerization initiator as a thermal polymerization initiator, or contains an azo polymerization initiator and a thermal polymerization initiator different from the azo polymerization initiator (non-azo polymerization initiator) can be implemented. In the method of using only an azo polymerization initiator, the effect of using an azo polymerization initiator can be maximized, and in the method of using an azo polymerization initiator and a non-azo polymerization initiator, the effect and characteristics based on the non-azo polymerization initiator can be utilized. In some methods, it is appropriate to set the proportion of the azo polymerization initiator to the total thermal polymerization initiator contained in the adhesive composition to about 10% by weight. From the perspective of effectively exerting the effect of the azo polymerization initiator, it is preferably 30% by weight or more, more preferably 40% by weight or more, and further preferably 50% by weight or more (for example, more than 50% by weight), and can be 55% by weight or more, or 60% by weight or more. In some other embodiments, the proportion of the azo polymerization initiator to the total thermal polymerization initiator is, for example, about 65% by weight or more, 75% by weight or more, 85% by weight or more, 95% by weight or more, or 99% by weight or more. In addition, the upper limit of the proportion of the azo polymerization initiator to the total thermal polymerization initiator is 100% by weight, for example, 90% by weight or less, 80% by weight or less, 70% by weight or less, or 60% by weight or less.

[0135] In the method of using an azo polymerization initiator as a thermal polymerization initiator, as a thermal polymerization initiator, a non-azo polymerization initiator used together with an azo polymerization initiator is not particularly limited, for example, a peroxide polymerization initiator, a redox polymerization initiator based on a combination of a peroxide and a reducing agent, a substituted ethane polymerization initiator, etc. can be used. Specifically, examples include: persulfates such as potassium persulfate and ammonium persulfate; peroxide compounds such as benzoyl peroxide (BPO), tert-butyl hydroperoxide, and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; redox initiators based on a combination of peroxides and reducing agents such as a combination of persulfates and sodium bisulfite, a combination of peroxides and sodium ascorbate; and so on. These non-azo polymerization initiators can be used alone or in combination of two or more. Although not particularly limited, in the technology disclosed herein, as a thermal polymerization initiator contained in the adhesive composition, it is preferably implemented in a manner of using an azo polymerization initiator and a peroxide polymerization initiator in combination.

[0136] Although not particularly limited, in the method of using a non-azo polymerization initiator as a thermal polymerization initiator, as the above-mentioned non-azo polymerization initiator, a non-azo polymerization initiator having a 10-hour half-life temperature of, for example, 50°C or more can be preferably used. From the viewpoint of the heat resistance of the non-azo polymerization initiator, the 10-hour half-life temperature of the above-mentioned non-azo polymerization initiator can be 55°C or more, 60°C or more, 65°C or more, or 70°C or more. It is appropriate that the upper limit of the 10-hour half-life temperature of the non-azo polymerization initiator is about 100°C or less (for example, less than 100°C), and can be 95°C or less, 90°C or less, 85°C or less, or 80°C or less.

[0137] The total amount of thermal polymerization initiators contained in the adhesive composition (when containing more than two kinds, the total content of more than two kinds) is set in a manner that can achieve easy peeling by heating. In some embodiments, the total amount of the above-mentioned thermal polymerization initiators is, for example, 0.1 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive composition. By making the adhesive composition and then the adhesive contain the above-mentioned amount of thermal polymerization initiator, the thermal polymerization initiator and the multifunctional monomer are fully in contact in the adhesive, so that the reaction of the two can proceed rapidly. Thus, an adhesive with easy peeling by heating can be formed. From the viewpoint of easy peeling by heating, the total amount of thermal polymerization initiators relative to 100 parts by weight of the above-mentioned polymer is preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight or more, further preferably 0.4 parts by weight or more, and can also be 0.5 parts by weight or more. The upper limit of the total amount of the thermal polymerization initiator in the adhesive composition is not particularly limited. In some embodiments, the total amount of the thermal polymerization initiator relative to 100 parts by weight of the polymer (specifically, the base polymer, such as an acrylic polymer) is, for example, about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), can be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), can be less than 0.9 parts by weight, can be less than 0.8 parts by weight, can be less than 0.7 parts by weight, and can also be less than 0.6 parts by weight. By setting the total amount of the thermal polymerization initiator to within the specified range, it is possible to obtain adhesive properties such as adhesive strength and storage stability, while ideally achieving an adhesive having efficient thermosetting properties and easy-to-remove properties by heating.

[0138] The content of the thermal polymerization initiator in the adhesive composition can also be determined by the relative relationship with the multifunctional monomer. In some ways, from the viewpoint of the contact probability with the multifunctional monomer, it is appropriate to set the amount of the thermal polymerization initiator relative to 100 parts by weight of the above-mentioned multifunctional monomer to be 0.1 parts by weight or more, preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight or more, further preferably 0.4 parts by weight or more, and also 0.5 parts by weight or more. In addition, in some other ways, for example, in the method of using a polymer with an ethylenically unsaturated group, from the viewpoint of the contact probability with the multifunctional monomer, it is appropriate to set the amount of the thermal polymerization initiator relative to 100 parts by weight of the multifunctional monomer to be 1.0 parts by weight or more, preferably 1.5 parts by weight or more, more preferably 3 parts by weight or more, further preferably 5 parts by weight or more, and also 7 parts by weight or more. In addition, the amount of the thermal polymerization initiator relative to 100 parts by weight of the multifunctional monomer can be, for example, about 20 parts by weight or less, can be 15 parts by weight or less, and can also be 12 parts by weight or less. In some embodiments, the amount of thermal polymerization initiator relative to 100 parts by weight of the multifunctional monomer is appropriately set to, for example, about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), can be less than 1.0 part by weight (for example, less than 1.0 part by weight), can be less than 0.9 part by weight, can be less than 0.8 part by weight, can be less than 0.7 part by weight, and can also be less than 0.6 part by weight.

[0139] (Crosslinking agent)

[0140] In the adhesive composition disclosed herein, crosslinking in the adhesive layer or crosslinking of the adhesive layer and its adjacent surface is the main purpose, and a crosslinking agent can be contained as required. The crosslinking agent is typically contained in the adhesive layer in the form after the crosslinking reaction. Through the use of a crosslinking agent, the cohesive force of the adhesive layer can be appropriately adjusted.

[0141] The kind of cross-linking agent is not particularly limited, and can be selected from among the cross-linking agents known in the past, for example, according to the composition of the adhesive composition, in the adhesive layer, the cross-linking agent plays a suitable cross-linking function. As usable cross-linking agents, isocyanate cross-linking agents, epoxy cross-linking agents, oxazoline cross-linking agents, aziridine cross-linking agents, carbodiimide cross-linking agents, melamine cross-linking agents, urea cross-linking agents, metal alkoxide cross-linking agents, metal chelate cross-linking agents, metal salt cross-linking agents, hydrazine cross-linking agents, amine cross-linking agents, etc. can be exemplified. They can be used alone or in combination of two or more. From the viewpoint of realizing adhesion and cohesion well at the same time, preferably isocyanate cross-linking agents, epoxy cross-linking agents, oxazoline cross-linking agents, aziridine cross-linking agents, carbodiimide cross-linking agents, particularly preferably isocyanate cross-linking agents.

[0142] As the isocyanate crosslinking agent, a polyfunctional isocyanate compound having two or more functions can be used. For example, aromatic isocyanates such as toluene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatephenyl)thiophosphate, and diphenylmethane diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; aliphatic isocyanates such as hexamethylene diisocyanate; and the like can be cited. Examples of commercially available products include isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name “Coronate L”), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name “Coronate HL”), isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, trade name “Coronate HX”), and trimethylolpropane / xylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., trade name “Takenate D-110N”).

[0143] As the epoxy crosslinking agent, a substance having two or more epoxy groups in one molecule can be used without particular limitation. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. Specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl meta-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, and the like. Commercially available products of epoxy crosslinking agents include trade names "TETRAD-X" and "TETRAD-C" manufactured by Mitsubishi Gas Chemical, trade name "EPICLON CR-5L" manufactured by DIC, trade name "Denacol EX-512" manufactured by Nagase Chemtex, trade name "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd., and the like.

[0144] As the oxazoline crosslinking agent, any oxazoline crosslinking agent having one or more oxazoline groups in one molecule can be used without particular limitation.

[0145] Examples of the aziridine crosslinking agent include trimethylolpropane tris[3-(1-aziridinyl)propionate] and trimethylolpropane tris[3-(1-(2-methyl)aziridinyl propionate)].

[0146] As the carbodiimide-based crosslinking agent, a low molecular weight compound or a high molecular weight compound having two or more carbodiimide groups can be used.

[0147] The amount used when a cross-linking agent is used (the total amount thereof when two or more cross-linking agents are used) is not particularly limited. From the perspective of realizing an adhesive that exerts adhesive properties such as bonding force and cohesive force in a well-balanced manner, the amount of the cross-linking agent used is an amount greater than 0 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive composition. The amount of the cross-linking agent used can be, for example, 0.001 parts by weight or more, 0.01 parts by weight or more, 0.1 parts by weight or more, or 0.5 parts by weight or more relative to 100 parts by weight of the above-mentioned polymer. In some embodiments, the amount of the cross-linking agent used is, for example, 1 part by weight or more, 1.5 parts by weight or more, 2 parts by weight or more, or 2.5 parts by weight or more relative to 100 parts by weight of the above-mentioned polymer. The upper limit of the amount of cross-linking agent used is not particularly limited. It is appropriate to set it to about 20 weight parts or less relative to 100 weight parts of the above-mentioned polymer (specifically, the base polymer. For example, an acrylic polymer). In some embodiments, it is preferably less than 10 weight parts, can be less than 7 weight parts, or can be less than 5 weight parts. By limiting the amount of cross-linking agent used, there is a tendency to easily obtain high adhesion. In addition, in some embodiments, the amount of cross-linking agent used is preferably less than 5 weight parts relative to 100 weight parts of the above-mentioned polymer, and can also be less than 3 weight parts. In some preferred embodiments, the amount of cross-linking agent used is less than 2 weight parts relative to 100 weight parts of the above-mentioned polymer, can be less than 1.5 weight parts (for example, less than 1.5 weight parts), can be less than 1.2 weight parts, can be less than 1.0 weight parts (for example, less than 1.0 weight parts), can be less than 0.8 weight parts, can be less than 0.6 weight parts, can be less than 0.5 weight parts, can be less than 0.4 weight parts, or can be less than 0.3 weight parts. It is believed that by limiting the amount of crosslinking agent used, the crosslinking density can be appropriately suppressed. Under this crosslinking density, during the heat treatment, the multifunctional monomer and the like frequently collide with the thermal polymerization initiator to perform thermal curing, which can increase the rate of reduction of the peeling force after heating, and show the desired easy peeling by heating and heat-resistant easy peeling. It should be noted that the technology disclosed herein is not limited to the above-mentioned investigation.

[0148] In order to more effectively carry out the cross-linking reaction, a cross-linking catalyst can be used. As the cross-linking catalyst, tetra-n-butyl titanate, tetraisopropyl titanate, triacetylacetonate iron, butyl tin oxide, dioctyltin dilaurate and other metal cross-linking catalysts are exemplified. The amount of the cross-linking catalyst used is not particularly limited. The amount of the cross-linking catalyst used can be set to about 0.0001 parts by weight or more, about 0.001 parts by weight or more, or about 0.005 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive composition, for example, 0.0001 parts by weight or more, about 0.001 parts by weight or more, or about 0.005 parts by weight or more, etc., in addition, it can be set to about 1 part by weight or less, about 0.1 parts by weight or less, or about 0.05 parts by weight or less, etc.

[0149] In the adhesive composition used for forming the adhesive layer, a compound that produces keto-enol tautomerism can be contained as a crosslinking retarder as desired. For example, in an adhesive composition containing an isocyanate crosslinking agent or an adhesive composition that can be used in combination with an isocyanate crosslinking agent, a compound that produces keto-enol tautomerism can be preferably used. Thus, the effect of extending the pot life of the adhesive composition can be exerted.

[0150] As compounds that produce keto-enol tautomerism, various β-dicarbonyl compounds can be used. As specific examples, β-diketones such as acetylacetone and 2,4-hexanedione; acetoacetic acid esters such as methyl acetoacetate and ethyl acetoacetate; propionylacetic acid esters such as ethyl propionylacetate; isobutyrylacetic acid esters such as ethyl isobutyrylacetate; malonates such as methyl malonate and ethyl malonate; and the like. Among them, acetylacetone and acetoacetic acid esters can be cited as suitable compounds. The compound that produces keto-enol tautomerism can be used alone or in combination of two or more.

[0151] The amount of the compound that produces keto-enol tautomerism used can be, for example, from 0.1 part by weight to 20 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer, for example, an acrylic polymer) contained in the adhesive composition, and it is appropriate to set it to from 0.5 part by weight to 15 parts by weight. For example, it can be from 1 part by weight to 10 parts by weight, and it can also be from 1 part by weight to 5 parts by weight.

[0152] (Monofunctional monomer)

[0153] In addition, in the adhesive composition, according to the expectation, one or more monofunctional monomers containing one ethylenically unsaturated group in one molecule may also be included. The monofunctional monomer can be used within the scope of the effect brought by the technology disclosed herein without damaging it. As the monofunctional monomer, known monofunctional acrylate monomers and vinyl monomers can be used. Although not particularly limited, the content of the monofunctional monomer in the adhesive composition is set to about 100 weight parts or less (0 weight parts or more and 100 weight parts or less) relative to 100 weight parts of the multifunctional monomer. For example, less than 100 weight parts) is appropriate, and can be less than 50 weight parts, less than 30 weight parts, less than 10 weight parts, or less than 1 weight part. The technology disclosed herein can be implemented in a manner that the adhesive composition does not substantially contain monofunctional monomers.

[0154] (Other ingredients)

[0155] As for the adhesive composition used for forming the adhesive layer, as required, various additives commonly used in the adhesive composition field such as adhesion imparting agent, silane coupling agent, release force modifier (surfactant, etc.), viscosity modifier (such as tackifier), leveling agent, plasticizer, filler, pigment, dye and other coloring agent, stabilizer, preservative, anti-aging agent, etc. can be included. For such various additives, conventionally known additives can be used by conventional methods, and since the present invention is not particularly characterized, detailed description is omitted.

[0156] It should be noted that the technology disclosed herein can achieve desired adhesive properties such as bonding strength without using an adhesion-imparting agent. In some embodiments, the content of the adhesion-imparting agent in the adhesive composition or even the adhesive can be, for example, less than 10 parts by weight, and further can be less than 5 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive composition. The content of the above-mentioned adhesion-imparting agent can be less than 1 part by weight (for example, less than 0.5 parts by weight), and can also be less than 0.1 parts by weight (0 parts by weight or more and less than 0.1 parts by weight). The adhesive composition can be a substance that does not contain an adhesion-imparting agent.

[0157] (Form of Adhesive Composition)

[0158] Although not particularly limited, the technology disclosed herein can be preferably implemented using a solvent-based adhesive composition. The above-mentioned solvent-based adhesive composition is an adhesive composition in the form of an adhesive-forming component contained in an organic solvent. The solvent-based adhesive composition typically contains a solution polymer of a monomer component, a multifunctional monomer and a thermal polymerization initiator, and optionally other additives. In the form of a solvent-based adhesive (layer), the effect brought about by the technology disclosed herein can be effectively exerted. The solvent contained in the solvent-based adhesive composition can be appropriately selected from conventionally known organic solvents. For example, any one solvent selected from the following, or a mixed solvent of two or more, can be used, namely: aromatic compounds such as toluene (typically aromatic hydrocarbons); esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropyl alcohol (for example, monohydric alcohols with 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; and the like.

[0159] As described above, according to the adhesive composition disclosed herein, an adhesive that cures when heated, such as being removed from an adherend by heating, or can be easily removed from an adherend after being heated at a high temperature, can be formed. Therefore, the adhesive composition disclosed herein, the adhesive formed by the adhesive composition, and the adhesive sheet having the adhesive (layer) can be respectively referred to as a thermosetting adhesive composition, a thermosetting adhesive, and a thermosetting adhesive sheet.

[0160] <Adhesive>

[0161] The adhesive disclosed herein can be formed, for example, using any of the above-mentioned adhesive compositions. The above-mentioned adhesive can be an adhesive formed by curing the adhesive composition by drying, crosslinking, polymerization, cooling, etc., i.e., a cured product of the above-mentioned adhesive composition. The curing means (e.g., drying, crosslinking, polymerization, cooling, etc.) of the adhesive composition can be applied to only one kind, or two or more kinds can be applied simultaneously or in multiple stages. In the case of a solvent-based adhesive composition, typically, the composition can be dried (preferably further crosslinked) to form an adhesive.

[0162] Forming adhesive (layer) by adhesive composition can be carried out by known methods in the past.After adhesive composition is given (for example, applied) to suitable surface, by suitably implementing curing treatment, adhesive can be formed with the form of stratiform (adhesive layer).For example, in the case of two-sided adhesive sheet without substrate, after adhesive composition is given to the surface (peel-off face) with releasability, by making this adhesive composition solidify and form adhesive layer (layer formed by adhesive) on this surface, thereby can form adhesive sheet.In addition, in the case of adhesive sheet with substrate, can preferably adopt by directly giving (typically coating) adhesive composition to this substrate and solidify and form the method (direct method) of adhesive layer.In addition, also can adopt by giving adhesive composition to the surface (peel-off face) with releasability and solidify and form adhesive layer on this surface, and this adhesive layer is transferred to the method (transfer method) of substrate.As above-mentioned peel-off face, can utilize the surface of release liner, the substrate back side through peeling treatment etc. It should be noted that the pressure-sensitive adhesive layer disclosed herein is typically formed continuously, but is not limited to such a form, and may be formed in a regular or random pattern such as dots or stripes.

[0163] The adhesive composition can be applied by using a known or commonly used coating machine such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a die coater, a rod coater, an air knife coater, or a spray coater. Alternatively, the adhesive composition can be applied by impregnation, curtain coating, or the like.

[0164] From the viewpoints of promoting the cross-linking reaction and improving the manufacturing efficiency, the drying of the adhesive composition is preferably carried out under heating. The drying temperature is not particularly limited, for example, it can be set to about 40 to 100°C, and is generally preferably set to about 60 to 80°C. For example, the heating temperature of the drying at the above temperature (for example, about 1 to 10 minutes, more specifically about 3 to 7 minutes) is low, and sometimes the volatilization of the solvent is also in progress, and the reaction of the multifunctional monomer and the deactivation of the polymerization initiator are negligible. In addition, after the adhesive composition is dried, it can be aged for the purpose of adjusting the transfer of components in the adhesive layer, carrying out the cross-linking reaction, and relaxing the strain that may exist in the substrate and the adhesive layer.

[0165] The adhesive disclosed herein contains the above-mentioned polymer (specifically, a base polymer, such as an acrylic polymer), a multifunctional monomer (such as a multifunctional acrylic monomer) and a thermal polymerization initiator. Except for the components that disappear due to the curing treatment (typically a solvent), the components contained in the adhesive formed by the adhesive composition disclosed herein and the content of each component are the same as the components contained and the content of the adhesive composition, so repeated descriptions are omitted. In some embodiments, from the perspective of effectively exerting the effects brought about by the technology disclosed herein, it is appropriate that the total proportion of the above-mentioned polymer, multifunctional monomer and thermal polymerization initiator to the whole adhesive is 50% by weight or more (for example, more than 50% by weight and less than 100% by weight), preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and can also be 95% by weight or more.

[0166] (Gel fraction)

[0167] The gel fraction of the adhesive (and the adhesive layer described later) is not particularly limited. In some embodiments, from the perspective of obtaining sufficient adhesion to the adherend and good heat-peelable properties, the initial (before heating) gel fraction (weight basis) of the adhesive (layer) is, for example, 85% or less, preferably 80% or less, more preferably 75% or less, can be 70% or less, can be 65% or less, or can be 60% or less. There is a tendency that those with a lower initial gel fraction tend to obtain a higher rate of reduction in peeling force after heating. In addition, from the perspective of obtaining adhesive layer formation, moderate cohesion, and retention, in some embodiments, the initial gel fraction of the adhesive (layer) is 20% or more, preferably 30% or more, more preferably 40% or more, further preferably 50% or more, can be 60% or more, or can be 70% or more. According to the adhesive having an appropriate initial gel fraction within the above range, there is a tendency for good heat curing reactivity.

[0168] In addition, it is preferred that the gel fraction of the adhesive (layer) after heating is higher than the gel fraction before heating. In some embodiments, the increase rate of the gel fraction of the adhesive (layer) after heating obtained by the following formula is preferably 10% or more, more preferably 20% or more, further preferably 30% or more, 40% or more, 50% or more, 60% or more, or 70% or more.

[0169] Gel fraction increase rate after heating [%] = (G1 / G0-1) × 100

[0170] (In the above formula, G1 is the gel fraction [%] of the adhesive (layer) after heat treatment at 180°C for 30 minutes, and G0 is the gel fraction [%] of the adhesive (layer) before heating).

[0171] The adhesive having the above-mentioned rate of increase in gel fraction after heating has the following tendency: it is easy to cure by heating, it is easy to obtain a high rate of reduction in peel force after heating, and it is easy to obtain excellent heat peelability and heat-resistant peelability. In addition, in some embodiments, the upper limit of the rate of increase in gel fraction after heating is appropriately set according to the target thermosetting property, for example, it can be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, or 30% or less.

[0172] Although not particularly limited, in some embodiments, from the viewpoint of the easy peelability by heating, the gel fraction (weight basis) of the adhesive (layer) after heating is appropriately 50% or more (e.g., more than 50%), preferably 60% or more, more preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and may be 95% or more. In addition, in some embodiments, the gel fraction of the adhesive (layer) after heating may be, for example, 99% or less, 95% or less, or 90% or less.

[0173] In addition, it is preferred that the change in gel fraction after storage of the adhesive (layer) relative to the gel fraction before heating is small. In some embodiments, the increase rate of gel fraction after storage of the adhesive (layer) obtained by the following formula is preferably 20% or less, more preferably 18% or less, and can be 16% or less, 12% or less, 8% or less, or 5% or less.

[0174] Gel fraction increase rate after storage [%] = (GS0 / G0-1) × 100

[0175] (In the above formula, GS0 is the gel fraction [%] of the adhesive (layer) after storage at 60°C for 7 days, and G0 is the gel fraction [%] of the adhesive (layer) before heating).

[0176] As described above, an adhesive in which the increase in gel fraction after storage is suppressed tends to have good storage stability. The lower limit of the increase in gel fraction after storage may be, for example, 1% or more, 5% or more, or 10% or more in practical terms.

[0177] Although not particularly limited, in some embodiments, from the viewpoint of maintaining adhesion and easy peelability by heating even after storage, the gel fraction (weight basis) of the adhesive (layer) after storage is, for example, 85% or less, preferably 80% or less, more preferably 75% or less, and may be 70% or less. In addition, in some embodiments, the gel fraction of the adhesive (layer) after storage is 20% or more, preferably 30% or more, more preferably 40% or more, further preferably 50% or more, and may be 60% or more, and may be 70% or more.

[0178] In addition, it is preferred that the gel fraction of the adhesive (layer) after storage and heating is higher than the gel fraction after storage. In some embodiments, the increase rate of the gel fraction after storage / heating of the adhesive (layer) obtained by the following formula is preferably 5% or more, more preferably 15% or more, further preferably 25% or more, and can be 30% or more, 35% or more, 40% or more, or 45% or more.

[0179] Gel fraction increase rate after storage / heating [%] = (GS1 / GS0-1) × 100

[0180] (In the above formula, GS1 is the gel fraction [%] of the adhesive (layer) after being stored in an environment of 60°C for 7 days and heated at 180°C for 30 minutes, and GS0 is the gel fraction [%] of the adhesive (layer) after being stored in an environment of 60°C for 7 days).

[0181] The adhesive having the above-mentioned storage / heating gel fraction increase rate has excellent storage stability, and even after storage, it is cured by heating, and it is easy to maintain a predetermined rate of reduction in the peeling force after heating, and it is easy to maintain the heat peelability and heat-resistant peelability. In addition, in some embodiments, the upper limit of the storage / heating gel fraction increase rate is appropriately set according to the target thermosetting property, for example, it can be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, or 30% or less.

[0182] Although not particularly limited, in some embodiments, from the viewpoint of the easy peelability after heating after storage, the gel fraction (weight basis) of the adhesive (layer) after storage / heating is appropriately 50% or more (e.g., more than 50%), preferably 60% or more, more preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and may be 95% or more. In addition, in some embodiments, the gel fraction of the adhesive (layer) after storage / heating may be, for example, 99% or less, or 95% or less.

[0183] The gel fraction of the adhesive can be adjusted mainly according to the monomer composition, Mw, amount of multifunctional monomer, type and amount of crosslinking agent, etc. of the polymer. In addition, the gel fraction after heating and the gel fraction after storage, and the gel fraction after storage / heating can be adjusted mainly according to the design of the polymer (for example, the introduction of ethylenically unsaturated groups, etc.), the type and amount of multifunctional monomer, and the type and amount of thermal polymerization initiator. Specifically, each of the above gel fractions is measured by the method described in the examples described later.

[0184] <Adhesive Sheet>

[0185] The adhesive sheet disclosed herein comprises an adhesive layer and is constituted. The adhesive constituting the above-mentioned adhesive layer is an adhesive (for example, a cured product of the adhesive composition) formed by any adhesive composition disclosed herein. The adhesive sheet can be an adhesive sheet with a substrate having the form of the above-mentioned adhesive layer on one or both sides of a non-peelable substrate (supporting substrate), or can be an adhesive sheet without a substrate such as the form in which the above-mentioned adhesive layer is retained in a release liner (that is, an adhesive sheet without a non-peelable substrate. Typically, an adhesive sheet formed by an adhesive layer). In the concept of the adhesive sheet mentioned herein, materials referred to as adhesive tapes, adhesive labels, adhesive films, etc. can be included. The adhesive sheet disclosed herein can be in a roll or in a monolithic form. Alternatively, it can be an adhesive sheet further processed into a form of various shapes.

[0186] The cross-sectional structure of the adhesive sheet is shown in Figure 1 .like Figure 1 As shown, the adhesive sheet 1 has an adhesive surface 1A, and is a single-sided adhesive sheet in which an adhesive layer 20 is provided on a surface 10A on one side of a sheet-like substrate layer (support substrate) 10. The adhesive sheet 1 is used in a manner that the surface 20A of the adhesive layer 20 as its adhesive surface 1A is pasted to an adherend. The back surface 10B of the substrate layer 10 (the surface on the opposite side to the surface 10A on one side) is also the back surface 1B of the adhesive sheet 1, constituting the outer surface of the adhesive sheet 1. The adhesive sheet 1 before use (i.e., before adhering to the adherend) can be a form of an adhesive sheet 50 with a release liner in which the adhesive surface 1A is protected by a release liner 30 on the adhesive layer 20 side as a release surface. Alternatively, it can also be a form of an adhesive sheet in which the surface (back surface) 10B on the other side of the substrate layer 10 becomes a release surface, and the adhesive layer 20 is abutted against the back surface by the adhesive sheet 1 being wound into a roll so that the surface (adhesive surface 1A) is protected.

[0187] (Adhesive layer)

[0188] The thickness of the adhesive layer is not particularly limited. The thickness of the adhesive layer is usually more than 1 μm, can be more than 2 μm, or can be more than 3 μm. There is a tendency that the greater the thickness of the adhesive layer, the higher the adhesion to the adherend. In some preferred embodiments, the thickness of the adhesive layer is more than 5 μm, can be more than 7 μm, or can be more than 9 μm. It is appropriate to set the upper limit of the thickness of the adhesive layer to about 200 μm or less, for example, it can be less than 100 μm (for example, less than 100 μm), or it can be less than 50 μm. By limiting the thickness of the adhesive layer within a specified range, the residual adhesive caused by cohesive failure is prevented from being generated, and there is a tendency to easily obtain easy peelability. In addition, a thin adhesive layer is advantageous in terms of thinning of adhesive sheets, and there is a tendency to have excellent followability to the adherend. In some preferred embodiments, the thickness of the adhesive layer is less than 40 μm, can be less than 30 μm (for example, less than 30 μm), can be less than 20 μm, or can be less than 15 μm.

[0189] (Base material layer)

[0190] The adhesive sheet disclosed herein may include a substrate layer. As a substrate (layer) supporting (lining) the adhesive layer, various sheet-like substrates can be used. As the above-mentioned substrate, resin film, paper, cloth, rubber sheet, foam sheet, metal foil, their composites, etc. can be used. As examples of resin films, polyolefin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers can be cited; polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); vinyl chloride resin film; vinyl acetate resin film; polyamide resin film; fluororesin film; cellophane; etc. As other examples of resin films, resin films formed by one or more engineering plastics (which may be super engineering plastics) in polyphenylene sulfide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyarylate resins, polyamideimide resins, and polyimide resins can be cited. The use of engineering plastics is preferred from the viewpoint of heat resistance. Examples of paper include Japanese paper, kraft paper, glassine, woodfree paper, synthetic paper, coated paper, etc. Examples of cloth include woven fabrics or nonwoven fabrics obtained by spinning various fibrous materials alone or in a blended manner. Examples of the above-mentioned fibrous materials include cotton, staple fibers, Manila hemp, pulp, rayon, acetate fibers, polyester fibers, polyvinyl alcohol fibers, polyamide fibers, polyolefin fibers, etc. Examples of rubber sheets include natural rubber sheets, butyl rubber sheets, etc. Examples of foam sheets include foamed polyurethane sheets, foamed polychloroprene rubber sheets, etc. Examples of metal foils include aluminum foil, copper foil, etc.

[0191] In some preferred embodiments, a resin film having a specified rigidity (strength) and excellent processability and operability is used as a substrate (layer). Among them, a polyester film is preferably used as the resin film substrate. It should be noted that in this specification, the so-called "resin film" is typically a non-porous film, and typically refers to a resin film that is substantially free of bubbles (voids). Therefore, the above-mentioned resin film is a concept that is different from a foam film and a non-woven fabric. The density of the resin film that can be used as a substrate can be about 0.85 to 1.50 g / cm 3 (e.g. 0.90 g / cm 3 ~1.20g / cm 3 , typically 0.92 g / cm 3 ~1.05g / cm 3 The resin film may be a single-layer structure or a multi-layer structure with two or more layers (eg, a three-layer structure).

[0192] The substrate layer (e.g., resin film) may be mixed with known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, antiblocking agents, etc. as needed. The amount of the additives is not particularly limited and can be appropriately set according to the application, etc.

[0193] The method for producing the resin film is not particularly limited, and for example, a conventionally known general resin film forming method such as extrusion molding, inflation molding, T-die casting, calender roll molding, etc. can be appropriately adopted.

[0194] The substrate layer may be substantially composed of a resin film. Alternatively, the substrate layer may include an auxiliary layer in addition to the resin film. Examples of the auxiliary layer include an optical property adjustment layer (e.g., a coloring layer, an antireflection layer), a printing layer for imparting a desired appearance, a laminating layer, an antistatic layer, a primer layer, a peeling layer, and other surface treatment layers.

[0195] The thickness of the substrate layer is not particularly limited, and can be appropriately selected according to the purpose, and can generally be 1 to 500 μm. From the viewpoints of processability, usability, operability, etc., it is appropriate that the thickness of the substrate layer is 2 μm or more (e.g., 3 μm or more, typically 5 μm or more), can be about 7 μm or more, or can be 10 μm or more. In addition, it is appropriate that the thickness of the substrate layer is about 200 μm or less, and from the viewpoint of lightweight and thin thickness, it is preferably about 100 μm or less, more preferably about 50 μm or less, can be 30 μm or less, can be 20 μm or less, or can be 15 μm or less. When the thickness of the substrate layer becomes smaller, there is a tendency to improve the softness of the adhesive sheet and the followability of the surface shape of the adherend.

[0196] The adhesive layer side surface of the substrate layer can be subjected to corona treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, coating of primer (primer) and other previously known surface treatments as needed. Such surface treatment can be used to improve the adhesion between the substrate layer and the adhesive layer, in other words, it can be a treatment for improving the anchoring of the adhesive layer to the substrate layer. The composition of the primer is not particularly limited and can be appropriately selected from known substances. The thickness of the primer layer is not particularly limited, for example, about 0.01 μm to 1 μm is appropriate, preferably about 0.1 μm to 1 μm. In addition, the back of the substrate layer can be subjected to the above-mentioned various surface treatments, antistatic treatment and other surface treatments.

[0197] (Total Thickness)

[0198] The total thickness of the adhesive sheet disclosed herein (which may include an adhesive layer and a substrate layer, but does not contain a release liner) is not particularly limited, and it is appropriate to set it in the range of about 5 to 1000 μm. From the perspectives of adhesive properties and usability, the total thickness of the adhesive sheet can be more than 10 μm, more than 15 μm, or more than 20 μm. In addition, from the perspective of lightweight and thin thickness, in some embodiments, the total thickness of the adhesive sheet is less than 500 μm, or less than 300 μm. In some preferred embodiments, the total thickness of the adhesive sheet is less than 100 μm (for example, less than 100 μm), more preferably less than 50 μm, or less than 30 μm. Reducing the thickness of the adhesive sheet is also advantageous in terms of filmization, miniaturization, lightweighting, and resource saving.

[0199] <Release liner>

[0200] The release liner used for the adhesive sheet disclosed herein is not particularly limited, and for example, a release liner having a release treatment on the surface of a liner substrate such as a resin film or paper, a release liner formed of a low-adhesive material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.) can be used. In the above release treatment, for example, a release treatment agent such as a silicone-based or long-chain alkyl-based release agent can be used. In some embodiments, a release-treated resin film can be preferably used as the release liner.

[0201] <Characteristics of adhesive sheets>

[0202] (Initial peel strength F0)

[0203] Although not particularly limited, it is appropriate that the initial peel strength (initial peel strength to glass plate) F0 of the adhesive sheet to the glass plate is 0.5N / 20mm or more, may be 0.8N / 20mm or more, and is preferably greater than 1.0N / 20mm. The adhesive sheet showing the above-mentioned initial peel strength F0 to the glass plate can exert good adhesion to the adherend. From the viewpoint of adhesion, the above-mentioned initial peel strength F0 to the glass plate may be 1.2N / 20mm or more, may be 1.5N / 20mm or more, may be 1.8N / 20mm or more, or may be 2.0N / 20mm or more. In some embodiments, the above-mentioned initial peel strength F0 to the glass plate is 3.0N / 20mm or more, may be 5.0N / 20mm or more, may be 7.0N / 20mm or more, may be 8.0N / 20mm or more, may be 9.0N / 20mm or more, or may be 10N / 20mm or more. The adhesive sheet having the above-mentioned initial peel strength F0 for the glass plate can exert sufficient adhesion during the period of bonding to the adherend. The upper limit of the initial peel strength F0 for the glass plate is appropriately set according to the required adhesion, and is therefore not limited to a specific range. For example, it can be about 20N / 20mm or less, about 10N / 20mm or less, about 5N / 20mm or less, or about 3N / 20mm or less. The above-mentioned initial peel strength F0 for the glass plate specifically refers to the peel strength of the glass plate measured at a peeling angle of 180 degrees and a speed of 300mm / min under an environment of 23°C. Considering the relative relationship with the peel strength F1 after heating, the above-mentioned initial peel strength F0 for the glass plate is also called the peel strength F0 of the glass plate before heating (peel strength of the glass plate before heating) of the glass plate. The above-mentioned initial peel strength F0 for the glass plate is more specifically measured by the method described in the embodiments described later.

[0204] (Peel strength after heating F1)

[0205] Although not particularly limited, it is appropriate that the peel strength F1 of the adhesive sheet to the glass plate after heating treatment at 180°C for 1 hour (peel strength to the glass plate after heating) is less than 3N / 20mm, and is preferably 1.0N / 20mm or less. The adhesive sheet showing the above-mentioned peel strength F1 to the glass plate after heating can become an adhesive sheet having easy peelability by heating, and further having heat-resistant easy peelability after heating treatment. From the viewpoint of peelability, the above-mentioned peel strength F1 to the glass plate after heating is preferably 0.8N / 20mm or less, more preferably 0.6N / 20mm or less, further preferably 0.5N / 20mm or less, and can be 0.4N / 20mm or less, or 0.3N / 20mm or less. The lower limit of the peel strength F1 to the glass plate after heating can be 0.0N / 20mm, or can be 0.01N / 20mm or more (for example, 0.1N / 20mm or more). The above-mentioned peel strength F1 of the glass plate after heating specifically refers to the peel strength of the glass plate measured at a peeling angle of 180 degrees and a speed of 300 mm / min in an environment of 23° C. after heating treatment at 180° C. for 1 hour in a state of being attached to an adherend. The above-mentioned peel strength F1 of the glass plate after heating is more specifically measured by the method described in the examples described later.

[0206] (Peel strength after 30 minutes heating)

[0207] Although not particularly limited, the peel strength of the adhesive sheet to the glass plate measured after heating at 180°C for 30 minutes (peel strength to the glass plate after 30 minutes of heating) is preferably 1.0N / 20mm or less. The adhesive sheet showing the above-mentioned peel strength to the glass plate after 30 minutes of heating has heating-easy peelability, can be easily peeled off by heat curing by short-term high-temperature heating, and can be easily peeled off from the adherend. From the viewpoint of peelability, it is appropriate that the peel strength to the glass plate after the above-mentioned 30 minutes of heating is 0.9N / 20mm or less, preferably 0.8N / 20mm or less, more preferably 0.6N / 20mm or less, further preferably 0.5N / 20mm or less, can be 0.4N / 20mm or less, and can also be 0.3N / 20mm or less. The lower limit of the peel strength to the glass plate after 30 minutes of heating can be 0.0N / 20mm, or it can be 0.01N / 20mm or more (for example, 0.1N / 20mm or more). The above-mentioned peel strength to a glass plate after heating for 30 minutes specifically refers to the peel strength to a glass plate measured at a peeling angle of 180 degrees and a speed of 300 mm / min under an environment of 23°C after heating at 180°C for 30 minutes in a state of being attached to an adherend. More specifically, the above-mentioned peel strength to a glass plate after heating for 30 minutes is measured in the same manner as the above-mentioned peel strength after heating F1 except that the heating treatment conditions are changed to 180°C for 30 minutes.

[0208] (Peel strength after storage FS0)

[0209] Although not particularly limited, the peel strength to the glass plate (peel strength to the glass plate after storage) FS0 of the adhesive sheet measured after storage at 60°C for 7 days is appropriately 0.5N / 20mm or more, and may be 0.8N / 20mm or more, and preferably greater than 1.0N / 20mm. For the adhesive sheet showing the above-mentioned peel strength to the glass plate FS0 after storage, good adhesion can be exhibited after storage regardless of long-term storage, temperature conditions during storage, etc. From the viewpoint of adhesion, the above-mentioned peel strength to the glass plate FS0 after storage may be 1.2N / 20mm or more, 1.5N / 20mm or more, or 1.8N / 20mm or more. In some embodiments, the above-mentioned peel strength FS0 to the glass plate after storage is 3.0N / 20mm or more, 5.0N / 20mm or more, 7.0N / 20mm or more, 8.0N / 20mm or more, 9.0N / 20mm or more, or 10N / 20mm or more. The adhesive sheet having the above-mentioned initial peel strength FS0 to the glass plate after storage can also exhibit good adhesion after storage. The upper limit of the peel strength FS0 to the glass plate after storage can be, for example, about 20N / 20mm or less, about 10N / 20mm or less, about 5N / 20mm or less, or about 3N / 20mm or less. The above-mentioned peel strength FS0 to the glass plate after storage specifically refers to the peel strength to the glass plate measured at a peeling angle of 180 degrees and a speed of 300mm / min at 23°C for the adhesive sheet after storage for 7 days at 60°C. The above-mentioned post-storage peel strength FS0 to the glass plate is more specifically measured by the method described in the examples described later.

[0210] (Peel strength after storage / heating FS1)

[0211] Although not particularly limited, for the adhesive sheet, it is appropriate that the peel strength to the glass plate measured after the adhesive sheet is stored at 60°C for 7 days and is attached to the glass plate as the adherend and heat-treated at 180°C for 1 hour (peel strength to the glass plate after storage / heating) FS1 is less than 3N / 20mm, preferably 1.0N / 20mm or less. The adhesive sheet showing the above-mentioned peel strength to the glass plate after storage / heating FS1 has heat-resistant easy peelability even when stored for a long time or when the temperature conditions during storage change, has heat-resistant easy peelability after heat treatment, and has good storage stability. From the viewpoint of peelability, the above-mentioned peel strength to the glass plate after storage / heating FS1 is preferably 0.8N / 20mm or less, more preferably 0.6N / 20mm or less, further preferably 0.5N / 20mm or less, particularly preferably 0.4N / 20mm or less, and may also be 0.3N / 20mm or less. The lower limit of the peel strength FS1 of the glass plate after storage / heating may be 0.0N / 20mm, or may be 0.01N / 20mm or more (e.g., 0.1N / 20mm or more). Specifically, the peel strength FS1 of the glass plate after storage / heating refers to the peel strength of the glass plate measured at a peeling angle of 180 degrees and a speed of 300mm / min after the adhesive sheet stored at 60°C for 7 days is attached to the glass plate as the adherend and subjected to a heating treatment at 180°C for 1 hour at 23°C. More specifically, the peel strength FS1 of the glass plate after storage / heating is measured by the method described in the examples described later.

[0212] (Peel force reduction rate after heating)

[0213] In some embodiments, the pressure-sensitive adhesive sheet preferably has a peel strength reduction rate A after heating calculated by the following formula of greater than 50%:

[0214] Reduction rate of peeling force after heating A[%] = (1-F1 / F0) × 100

[0215] (In the above formula, F1 is the peel strength after heating [N / 20mm] measured at 23°C after being attached to a glass plate and heated at 180°C for 1 hour, and F0 is the peel strength before heating of the glass plate [N / 20mm]).

[0216] The adhesive sheet satisfying the above characteristics can be well bonded to the adherend, and can play a good heating peelability and heat-resistant peelability when peeled after the heat treatment. In some preferred embodiments, the above-mentioned peeling force reduction rate A after heating can be 60% or more, 70% or more, 80% or more, 90% or more, 95% or more, or 98% or more. The larger the peeling force reduction rate A after heating, the more excellent heating peelability and heat-resistant peelability can be played. In addition, it is preferred that the peeling force reduction rate A after heating is less than 99.9%. According to the adhesive sheet having a peeling force reduction rate A after heating of less than 99.9%, after heating, the adhesive sheet can maintain the bonding state with the adherend and have the desired peelability to the adherend. Thus, the situation in which the adhesive sheet is naturally peeled off from the adherend by heating and the resulting adverse conditions are prevented. From the above viewpoint, the peeling force reduction rate A after heating can be less than 99.0%, for example, it can also be less than 95.0%.

[0217] (Peel force reduction rate after storage / heating)

[0218] In some embodiments, the pressure-sensitive adhesive sheet preferably has a peel strength reduction rate B after storage / heating calculated by the following formula of more than 50%:

[0219] Peel force reduction rate after storage / heating B[%] = (1-FS1 / FS0) × 100

[0220] (In the above formula, FS1 is the peel strength after storage / heating measured at 23°C after the adhesive sheet is adhered to a glass plate after being stored at 60°C for 7 days and heated at 180°C for 1 hour [N / 20mm], and FS0 is the peel strength before heating of the adhesive sheet to the glass plate after being stored at 60°C for 7 days [N / 20mm]).

[0221] The storage stability of the adhesive sheet satisfying the above characteristics is excellent, so even after storage, when peeled after heat treatment, it can also play a good heating easy peeling property and heat-resistant easy peeling property. In some preferred embodiments, the above-mentioned peeling force reduction rate B after storage / heating can be more than 60%, more than 70%, more than 80%, more than 90%, more than 95%, or more than 98%. The larger the peeling force reduction rate B after storage / heating, the better the storage stability. In addition, it is preferred that the peeling force reduction rate B after storage / heating is less than 99.9%. According to the adhesive sheet with a peeling force reduction rate B after storage / heating lower than 99.9%, after the adhesive sheet is stored for a specified period of time and is pasted to the adherend and heated, the adhesive sheet remains in a bonding state with the adherend, and has the desired easy peeling property to the adherend. Thus, the situation where the adhesive sheet is naturally peeled off from the adherend by heating and the resulting undesirable situation are prevented. From the above viewpoints, the peel force reduction rate B after storage / heating may be 99.0% or less, for example, less than 95.0%.

[0222] (F1 / F0)

[0223] In some embodiments, the peel strength F1 [N / 20mm] of the adhesive sheet after heating is less than 100% of the initial peel strength F0. In other words, the ratio (F1 / F0) of the adhesive sheet is less than 1. It is appropriate that the above ratio (F1 / F0) is less than 0.5, preferably less than 0.4, more preferably less than 0.3, further preferably less than 0.2, and may also be less than 0.15. The adhesive sheet that meets this characteristic is well bonded to the adherend, and when peeled after the heat treatment, it can exhibit good heating peelability and heat-resistant peelability. The lower limit of the above ratio (F1 / F0) is not particularly limited, for example, it can be about 0.01 or more.

[0224] (FS1 / FS0)

[0225] In some embodiments, the storage / post-heating peel strength FS1 [N / 20mm] of the adhesive sheet is lower than 100% of the post-storage peel strength FS0. In other words, the ratio (FS1 / FS0) of the adhesive sheet is lower than 1. It is appropriate that the above (FS1 / FS0) is less than 0.5, preferably less than 0.4, more preferably less than 0.3, further preferably less than 0.2, and may also be less than 0.15. The adhesive sheet satisfying this characteristic is well bonded to the adherend even after storage, and exhibits good heat peelability and heat-resistant peelability when peeled off after heat treatment, so it has excellent storage stability. The lower limit of the above ratio (FS1 / FS0) is not particularly limited, for example, it may be greater than about 0.01.

[0226] (Total amount of released gas when kept at 180℃ for 1 hour)

[0227] In some embodiments, the total amount of gas released when the adhesive sheet is kept at 180°C for 1 hour is preferably 1000 μg or less (also referred to as 1000 μg / g or less) per 1 g of the adhesive sheet. In an adhesive sheet that satisfies this characteristic, the gas released from the adhesive sheet is limited to a specified amount or less, so it is not easy to cause adverse conditions caused by the released gas (such as adherend contamination, reduced vacuum, etc.). From this point of view, in some preferred embodiments, the total amount of gas released when the adhesive sheet is kept at 180°C for 1 hour is 950 μg / g or less, more preferably 900 μg / g or less, further preferably 850 μg / g or less, particularly preferably 800 μg / g or less, and may be 750 μg / g or less, or 700 μg / g or less. The lower the lower limit of the total amount of gas released when the adhesive sheet is kept at 180°C for 1 hour, the more preferred it is, and it may be about 1 μg / g or more (for example, 10 μg / g or more or 100 μg / g or more).

[0228] The total amount of gas released when the adhesive sheet is kept at 180°C for 1 hour is measured by using the adhesive sheet as a measurement sample and analyzing the released gas when it is kept at 180°C for 1 hour using gas chromatography-mass spectrometry (GC / MS). 2 The specific measurement conditions are as follows.

[0229] (Analysis device)

[0230] Heating device: GERSTEL, TDU2

[0231] GC / MS: Agilent Technologies, 8890 / 5977B

[0232] (Measurement conditions)

[0233] TDU conditions (sample): 30℃(1min)→720℃ / min→180℃(60min)

[0234] TDU conditions (standard product): 30℃(1min)→720℃ / min→300℃(5min)

[0235] CIS conditions: -150℃(2.5min)→12℃ / sec→300℃(10min)

[0236] GC / MS conditions

[0237] Chromatographic column: HP-Ultra1( df=0.33μm)

[0238] Column temperature: 40℃(5min)→10℃ / min→100℃→20℃ / min→300℃(9min)

[0239] Column pressure: Constant flow mode (113kPa, Vac)

[0240] Column flow rate: 1mL / min (He)

[0241] Injection method: CIS, Split (20:1)

[0242] Detector: MS

[0243] Ion source temperature: 230°C

[0244] Ionization method: EI (70eV)

[0245] <Peeling method>

[0246] According to the present specification, a method for peeling an adhesive sheet adhered to an adherend from the adherend is provided. The peeling method includes: after the adherend to which the adhesive sheet is adhered is subjected to a heat treatment at a temperature higher than 150°C, the adhesive sheet is peeled from the adherend. The adhesive sheet disclosed herein has heat-resistant peelability, so it can be easily peeled from the adherend even after being exposed to heating exceeding 150°C. In addition, the adhesive sheet has good storage stability, so even if it is assumed to be stored for a long time, and regardless of the temperature conditions during storage, the heat-resistant peelability (heat-resistant peelability) can be maintained.

[0247] The temperature of the heat treatment of the adherend to which the adhesive sheet is attached can be above 160°C, or above 170°C. The upper limit of the heat treatment temperature may vary depending on the purpose of the heat treatment, the heat resistance of the adherend, etc., but is generally below 250°C, and may be below 230°C or below 200°C. The time of the heat treatment is not particularly limited, and may be above 3 minutes, above 5 minutes, above 7 minutes, or above 9 minutes. In addition, from the perspective of the efficiency of the heating process, the heat treatment time may be within 1 hour, within 30 minutes, within 15 minutes, or within 10 minutes. The adhesive sheet disclosed herein is heat-cured by the above-mentioned short-time high-temperature heat treatment to thermally cure the adhesive, and can show easy peeling by heating. In addition, in some embodiments, the heat treatment time may be above 10 minutes, above 30 minutes, above 60 minutes, more than 1 hour, more than 3 hours, more than 4 hours, or more than 5 hours. For the adhesive sheet disclosed herein, the adhesive is thermally cured by the above-mentioned high temperature heating treatment, the peeling force is reduced, or the increase of the peeling force is suppressed, and even if the heating state continues for a long time, the increase of the peeling force (heavy peeling) will not occur or be suppressed. Therefore, the heating easy peelability (heat-resistant easy peelability) can be maintained after a long heating treatment. The upper limit of the heating treatment time is not particularly limited, but from the viewpoint of the efficiency of the heating process, it can be within 10 hours, within 5 hours, or within 3 hours.

[0248] In addition, the above-mentioned adhesive sheet can be an adhesive sheet having the desired adhesive properties even if it is stored for a specified period before being attached to the adherend. The adhesive sheet disclosed herein has good storage stability, so, for example, even if it is exposed to a temperature of 40°C or above (for example, 40°C or above and below 100°C), or even 50°C or above, 60°C or above, it can maintain the desired adhesive properties and heat-peelable properties. In addition, even in an environment below 40°C, for example, when stored for a long time for more than 30 days, more than 100 days, or even half a year or more than a year, the adhesive properties originally designed will also change. In particular, with respect to adhesives having heat-peelable properties, there is a risk that the heat-polymerization initiator will decompose due to long-term storage, and the desired heat-peelable properties will be damaged for adhesives containing thermal polymerization initiators, but the adhesive sheet disclosed herein has heat-peelable properties and good storage stability, so regardless of long-term storage, temperature conditions during storage, etc., it can also exert heat-peelable properties after storage, and has high utilization value.

[0249] <Application>

[0250] The adhesive sheet disclosed herein has heat-removable properties, so it can be used as an adhesive sheet for various purposes requiring heat-removable properties, such as the use of peeling and removing from the adherend by heating. For example, in the state of being attached to the adherend, it can be preferably used for purposes that are exposed to heating exceeding 150°C (exceeding 150°C and about 250°C or less, for example, above 160°C, and further above 170°C). As such uses, for example, masking uses, temporary fixing uses, and protective uses that require heat resistance for the adhesive sheet can be cited. In addition, for example, it can also be preferably used as a process material that is fixed to the adherend and peeled off in the manufacturing process of electronic equipment and electronic components. In addition, as a suitable use of the adhesive sheet disclosed herein, semiconductor element manufacturing purposes can be cited. For example, in semiconductor wafer processing (typically silicon wafer processing), it can be preferably used as a wafer fixing sheet that fixes the wafer to a fixing plate. In addition, the adhesive sheet disclosed herein can also be preferably used as a protective sheet for protecting the wafer in the above-mentioned wafer processing. In particular, when semiconductor elements are manufactured, they are exposed to heating during processing steps, etc., so it is preferred to use an adhesive sheet with heat resistance and easy peelability. In addition, the adhesive sheet disclosed herein can also be applied to optical uses that require heat resistance. More specifically, for example, as an optical adhesive sheet for use in bonding optical components (optical component bonding), for the manufacture of products (optical products) using the above-mentioned optical components, the adhesive sheet disclosed herein can be used. It should be noted that the above-mentioned optical component refers to a component having optical properties (for example, polarization, light refraction, light scattering, light reflectivity, light transmittance, light absorption, light diffraction, optical rotation, visual recognition, etc.).

[0251] In addition, the release gas of the adhesive sheet involved in some preferred embodiments is reduced, so it can be preferably used for various purposes where the release gas is not expected. For example, if the release gas component from the adhesive sheet is large, the adherend is contaminated due to the release gas component, which can be the cause of undesirable conditions such as poor appearance. Therefore, in the use exposed to the above-mentioned heating, it is desirable to suppress the amount of released gas from the adhesive sheet. In addition, for example, in the use of using pressure difference to temporarily fix materials, the use of adhesion of adhesive sheets, and the use of processing adherends under vacuum, the adhesive sheet can be used in a vacuum or reduced pressure environment. In these uses, if the release gas amount from the adhesive sheet is large, the vacuum degree is reduced, which can be the cause of undesirable conditions. The above-mentioned adhesive sheet can be used for various uses including the above-mentioned uses where the release gas is not expected.

[0252] The type of material (adherend material) disclosed herein for pasting is not particularly limited. The adhesive sheet disclosed herein can be used for fixing and protecting various components and materials. As examples of adherend materials, for example, it can be: glasses such as alkaline glass and alkali-free glass; metal materials such as stainless steel (SUS) and aluminum; ceramic materials such as alumina and silica; resin materials such as polyester resins such as PET, acrylic resins, ABS resins, polycarbonate resins, polystyrene resins, and transparent polyimide resins; and so on. As suitable examples of adherend materials, for example, glass materials such as alkaline glass, semiconductor chips, etc. can be cited. The above-mentioned glass material can be, for example, a glass plate having a surface with a transparent conductive film (such as ITO (indium tin oxide) film) and FPC (flexible circuit board) that can be used for tablet personal computers, mobile phones, organic LEDs (light emitting diodes), etc.

[0253] The matters disclosed in this specification include the following.

[0254] [1] An adhesive composition comprising a polymer, a multifunctional monomer and a thermal polymerization initiator, wherein:

[0255] The content of the polyfunctional monomer is 50 parts by weight or more relative to 100 parts by weight of the polymer.

[0256] The thermal polymerization initiator comprises an azo polymerization initiator,

[0257] The content of the azo polymerization initiator is 0.1 parts by weight or more based on 100 parts by weight of the polymer.

[0258] [2] The pressure-sensitive adhesive composition according to [1] above, comprising an acrylic polymer as the polymer.

[0259] [3] The adhesive composition according to [1] or [2] above, comprising a polyfunctional acrylate monomer as the polyfunctional monomer.

[0260] [4] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of [1] to [3] above.

[0261] [5] An adhesive sheet having an adhesive layer, wherein:

[0262] The adhesive layer comprises a polymer, a multifunctional monomer and a thermal polymerization initiator.

[0263] The content of the polyfunctional monomer is 50 parts by weight or more relative to 100 parts by weight of the polymer.

[0264] The thermal polymerization initiator comprises an azo polymerization initiator,

[0265] The content of the azo polymerization initiator is 0.1 parts by weight or more based on 100 parts by weight of the polymer.

[0266] [6] The pressure-sensitive adhesive sheet according to [4] or [5] above, wherein the pressure-sensitive adhesive layer contains an acrylic polymer as the polymer.

[0267] [7] The pressure-sensitive adhesive sheet according to [5] or [6] above, wherein the pressure-sensitive adhesive layer contains a polyfunctional acrylate monomer as the polyfunctional monomer.

[0268]

[11] An adhesive sheet having an adhesive layer, wherein:

[0269] The adhesive layer comprises a polymer, a multifunctional monomer and a thermal polymerization initiator.

[0270] The self-accelerating decomposition temperature (SADT) [°C] of the aforementioned thermal polymerization initiator satisfies the following formula:

[0271] SADT+10≥60.

[0272]

[12] The pressure-sensitive adhesive sheet according to

[11] above, wherein the post-heating peel strength reduction rate A [%] determined by the following formula is higher than 50% and lower than 99.9%.

[0273] Reduction rate of peeling force after heating A[%] = (1-F1 / F0) × 100

[0274] (In the above formula, F1 is the peel strength after heating [N / 20mm] measured at 23°C after being attached to a glass plate and heated at 180°C for 1 hour, and F0 is the peel strength before heating of the glass plate [N / 20mm])

[0275]

[13] The pressure-sensitive adhesive sheet according to

[11] or

[12] above, wherein the polymer contains an ethylenically unsaturated group.

[0276]

[14] The pressure-sensitive adhesive sheet according to any one of

[11] to

[13] above, wherein the pressure-sensitive adhesive layer contains a polyfunctional acrylate monomer as the polyfunctional monomer.

[0277]

[15] The pressure-sensitive adhesive sheet according to any one of

[11] to

[14] above, wherein the content of the polyfunctional monomer in the pressure-sensitive adhesive layer is less than 45 parts by weight based on 100 parts by weight of the polymer.

[0278]

[16] The adhesive sheet according to any one of

[11] to

[15] above, wherein the content of the thermal polymerization initiator in the adhesive layer is 0.1 parts by weight or more based on 100 parts by weight of the polymer.

[0279]

[21] A peeling method, which is a method for peeling the pressure-sensitive adhesive sheet according to any one of [4] to

[16] above, which is adhered to an adherend, the peeling method comprising:

[0280] A step of subjecting the adherend to which the pressure-sensitive adhesive sheet is attached to the adherend to a heat treatment at a temperature higher than 150° C., and then peeling the pressure-sensitive adhesive sheet from the adherend.

[0281] Example

[0282] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the contents shown in these embodiments. It should be noted that, unless otherwise specified, in the following description, "parts" and "%" are based on weight.

[0283] <Evaluation Method>

[0284] (Initial peel strength (peel strength before heating) F0)

[0285] The adhesive sheet is cut into a size of 20mm in width and 100mm in length. Under the environment of 23°C and 50%RH, a 2kg roller is reciprocated once to press the adhesive surface of the adhesive sheet and make it adhere to the alkaline glass plate (made by Matsunami Glass Industry Co., Ltd., with a thickness of 1.35mm and a blue plate edge grinding product) as the adherend. Under the same environment, the alkaline glass plate with the above-mentioned adhesive sheet is left to stand for 6 hours and used as an evaluation sample. The above-mentioned evaluation sample is set in a tensile testing machine under the environment of 23°C and 50%RH, and the peel strength (initial peel strength) F0 [N / 20mm width) when the adhesive sheet is peeled off from the adherend under the conditions of a peeling angle of 180 degrees and a speed of 300mm / minute is measured. As a tensile testing machine, the product name "EZ-S 500N" made by Shimadzu Company or its equivalent can be used. In addition, when the evaluation object is a double-sided adhesive sheet, the non-measurement surface can be lined with a PET film to implement the measurement.

[0286] (Peel strength after heating F1)

[0287] Using an adhesive sheet, an evaluation sample is prepared by the method described in the above-mentioned determination of the initial peel strength F0. The obtained evaluation sample is heat-treated in an oven at 180°C for 1 hour, taken out of the oven, and allowed to stand for 30 minutes under an environment of 23°C and 50% RH. Then, the above-mentioned evaluation sample is set in a tensile testing machine under the same environment, and the peel strength (peel strength after heating) F1 [N / 20mm width) when the adhesive sheet is peeled off from the adherend at a peeling angle of 180 degrees and a speed of 300mm / min is measured. Regarding the adherend, the tensile testing machine, and other matters, the determination of the initial peel strength F0 is the same.

[0288] (Peel strength after storage FS0)

[0289] The adhesive sheet was stored at 60°C for 7 days. The evaluation sample was prepared by the method described in the above-mentioned determination of the initial peel strength F0 using the adhesive sheet after the above-mentioned storage. Then, the peel strength (peel strength after storage) FS0 [N / 20 mm width) was measured by the same method as the method described in the above-mentioned initial peel strength F0. The adherend, tensile testing machine, and other matters were the same as those for the determination of the initial peel strength F0.

[0290] (Peel strength after storage / heating FS1)

[0291] The adhesive sheet is stored at 60°C for 7 days. Using the adhesive sheet after storage, an evaluation sample is prepared by the method described in the above-mentioned determination of the initial peel strength F0. The obtained evaluation sample is heat-treated in an oven at 180°C for 1 hour and allowed to stand for 30 minutes in an environment of 23°C and 50% RH. Then, the evaluation sample is placed in a tensile testing machine under the same environment, and the peel strength (storage / after-heating peel strength) FS1 [N / 20mm width) when the adhesive sheet is peeled off from the adherend at a peeling angle of 180 degrees and a speed of 300mm / min is measured. Regarding the adherend, the tensile testing machine, and other matters, it is the same as the determination of the initial peel strength F0.

[0292] (Gel fraction)

[0293] The gel fraction (weight ratio of the ethyl acetate insoluble component) of the pressure-sensitive adhesive layer can be measured by the following method.

[0294] About 0.1 g of the adhesive sample (weight Wg1) was wrapped into a purse shape with a porous polytetrafluoroethylene membrane (weight Wg2) with an average pore size of 0.2 μm, and the mouth was tied with a kite string (weight Wg3). As the porous polytetrafluoroethylene (PTFE) membrane, the trade name "Nitoflon (registered trademark) NTF1122" (average pore size 0.2 μm, porosity 75%, thickness 85 μm) available from Nitto Denko Corporation or its equivalent was used.

[0295] The package was immersed in 50 mL of ethyl acetate and kept at room temperature (typically 23° C.) for 7 days to dissolve only the sol component in the adhesive layer outside the film, then the package was taken out and the ethyl acetate attached to the outer surface was wiped off, and the package was dried at 130° C. for 2 hours, and the weight of the package was measured (Wg4). Then, each value was substituted into the following formula to obtain the gel fraction of the adhesive layer.

[0296] Gel fraction [%] = [(Wg4-Wg2-Wg3) / Wg1] × 100

[0297] Regarding the gel fraction of the adhesive layer, the following gel fractions were measured respectively: initial (gel fraction before heating); the adhesive layer was heated in an oven at 180°C for 30 minutes, taken out of the oven, and allowed to stand for 30 minutes in an environment of 23°C and 50% RH (gel fraction after heating); the adhesive layer was stored in an environment of 60°C for 7 days (gel fraction after storage); the adhesive layer was stored in an environment of 60°C for 7 days, heated in an oven at 180°C for 30 minutes, and allowed to stand for 30 minutes in an environment of 23°C and 50% RH (gel fraction after storage / heating).

[0299] <Example 1>

[0300] (Preparation of Adhesive Composition)

[0301] Into a reaction container equipped with a cooling tube, a nitrogen introduction tube, a thermometer and a stirring device, 85 parts of methoxyethyl acrylate (MEA), 10 parts of N-vinyl-2-pyrrolidone (NVP), 5 parts of 4-hydroxybutyl acrylate (4HBA) and 0.5 parts of acrylic acid (AA) as monomer components, 300 parts of ethyl acetate as a polymerization solvent, and 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator were added, and a polymerization reaction (solution polymerization) was carried out at 61° C. for 6 hours under a nitrogen atmosphere, thereby obtaining a solution containing an acrylic polymer A.

[0302] To the solution of the acrylic polymer A, 70 parts of dipentaerythritol hexaacrylate (DPHA) as a multifunctional monomer, 3 parts of an isocyanate crosslinking agent (manufactured by Mitsui Chemicals, product name “Takenate D-101E”), 0.2 parts of benzoyl peroxide (manufactured by NOF Corporation, product name “NYPER BMT 40SV”, 10-hour half-life temperature: 73° C., SADT: 45° C.) as a thermal polymerization initiator, and 0.3 parts of an azo polymerization initiator A1 (manufactured by FUJIFILM Wako Pure Chemical Corporation, product name “VAm-110”, 2,2′-azobis(N-butyl-2-methylpropionamide), 10-hour half-life temperature: 110° C., SADT: 70° C.) were added relative to 100 parts of the acrylic polymer A, and the mixture was uniformly mixed to prepare the solvent-based adhesive composition involved in this example.

[0303] (Production of Adhesive Sheet)

[0304] The adhesive composition obtained in the above manner was applied to the release surface of a commercially available PET release liner and dried at 80°C for 5 minutes to form an adhesive layer with a thickness of 10 μm. A PET film with a thickness of 12 μm was attached to the adhesive layer to prepare the adhesive sheet (single-sided adhesive sheet with a substrate) involved in this example. The adhesive surface of the above-mentioned adhesive sheet was protected by the release liner.

[0305] <Examples 2 to 7 and Comparative Examples 1 and 2>

[0306] The adhesive compositions of each example were prepared by the same method as in Example 1 except that the type and amount of the thermal polymerization initiator were changed as shown in Table 1, and the single-sided adhesive sheet with a substrate of each example was produced by using the obtained adhesive compositions in the same manner as in Example 1. It should be noted that in Table 1, the azo polymerization initiator A2 represents 1,1'-azobis(1-cyclohexanecarboxylic acid) dimethyl ester (manufactured by FUJIFILM Wako Pure Chemical Corporation, product name "VE-073", 10-hour half-life temperature: 73°C, SADT: 75°C), and the azo polymerization initiator A3 represents AIBN (10-hour half-life temperature: 65°C, SADT: 50°C).

[0307] <Example 8>

[0308] (Preparation of Adhesive Composition)

[0309] In a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer and a stirring device, 100 parts of monomer components containing MEA, acryloylmorpholine (ACMO) and hydroxyethyl acrylate (HEA) at a molar ratio of 80:20:20 and 65 parts of toluene as a polymerization solvent were charged, and 0.2 parts of benzoyl peroxide as a thermal polymerization initiator was added, and a polymerization reaction (solution polymerization) was carried out at 61° C. for 6 hours under a nitrogen atmosphere to obtain a solution containing an acrylic polymer B. Methacryloxyethyl isocyanate (MOI) in an amount equivalent to 16 mol relative to 20 mol of HEA used as a raw material of the acrylic polymer b was added to the solution of the acrylic polymer b, and an addition reaction treatment was carried out at 50° C. for 48 hours in an air flow, thereby obtaining a solution of an acrylic polymer B having a methacryloyl group at the end of a side chain.

[0310] To the solution of the acrylic polymer B, 30 parts of DPHA as a multifunctional monomer, 0.5 parts of the isocyanate crosslinking agent, and 0.5 parts of benzoyl peroxide (manufactured by NOF Corporation, product name "NYPER BW", 10-hour half-life temperature: about 73°C, SADT: 75°C) as a thermal polymerization initiator were added relative to 100 parts of the acrylic polymer B, and the mixture was uniformly mixed to prepare the solvent-based adhesive composition involved in this example.

[0311] (Production of Adhesive Sheet)

[0312] The adhesive composition obtained in the above manner was applied to the release surface of a commercially available PET release liner and dried at 80°C for 5 minutes to form an adhesive layer with a thickness of 30 μm. A polyimide (PI) film (product name "Kapton 200H", made by Du Pont-toray Co., Ltd.) with a thickness of 50 μm was attached to the adhesive layer and aged at 50°C for 3 days. Thus, the adhesive sheet (single-sided adhesive sheet with a substrate) involved in this example was prepared. The adhesive surface of the above-mentioned adhesive sheet is protected by a release liner.

[0313] <Examples 9 to 22 and Comparative Examples 3 and 4>

[0314] Except for changing the type and amount of the multifunctional monomer, the amount of the cross-linking agent, and the type and amount of the thermal polymerization initiator as shown in Tables 2 to 3, the adhesive composition involved in each example was prepared by the same method as in Example 8, and the single-sided adhesive sheet with a substrate involved in each example was prepared using the obtained adhesive composition in the same manner as in Example 8. In addition, in Tables 2 and 3, NYPER BMT represents the product name “NYPER BMT” (manufactured by NOF Corporation, 10-hour half-life temperature: 73° C., SADT: 45° C.), AIBN represents 2,2′-azobisisobutyronitrile (10-hour half-life temperature: 65° C., SADT: 50° C.), VR-110 represents 2,2′-azobis(2,4,4-trimethylpentane) (manufactured by FUJIFILM WakoPure Chemical Corporation, product name “VR-110”, 10-hour half-life temperature: 110° C., SADT: 98° C.), PERBUTYL Z represents the product name “PERBUTYL Z” (manufactured by NOF Corporation, tert-butyl peroxybenzoate, 10-hour half-life temperature: 104.3° C., SADT: 65° C.), and PERHEXYNE 25B represents the product name “PERHEXYNE 25B" (manufactured by NOF Corporation, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3-yl, 10-hour half-life temperature: 128.4°C, SADT: 90°C)), PERCUMYL H represents the product name "PERCUMYL H-80" (manufactured by NOF Corporation, cumene hydroperoxide, 10-hour half-life temperature: 157.9°C, SADT: 80°C), and HDDA represents 1,6-hexanediol diacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.).

[0315] Tables 1 to 3 show the summary and evaluation results of each example.

[0316] [Table 1]

[0317]

[0318] [Table 2]

[0319]

[0320] [Table 3]

[0321] Table 3

[0322]

[0323] As shown in Tables 1 to 3, the adhesive sheets involved in the embodiments using an adhesive comprising a polymer, a multifunctional monomer and a thermal polymerization initiator, and the SADT of the thermal polymerization initiator satisfies the formula: SADT+10≥60, have easy peelability after heating before and after storage. On the other hand, the adhesive sheets involved in the comparative examples using a thermal polymerization initiator that does not satisfy the above formula have an increase in the peel strength FS1 after heating after being stored at 60°C for 1 week. In addition, the peel force reduction rate after heating of the adhesive sheets involved in the above embodiments is more than 50% and less than 99.9%. According to the above results, by using a thermal polymerization initiator that satisfies the above formula together with a polymer and a multifunctional monomer, an adhesive sheet with good easy peelability after heating and good storage stability can be obtained.

[0324] In addition, as shown in Table 1, the adhesive compositions of Examples 1 to 7 contain 50 parts or more of a multifunctional monomer relative to 100 parts of the polymer and 0.1 parts or more of an azo polymerization initiator. The adhesive sheet having an adhesive layer formed from the adhesive composition has a peel strength F1 of 1.0 N / 20 mm or less after heating at 180°C for 1 hour, and a peel strength FS1 after heating after storage at 60°C for 1 week is also 1.0 N / 20 mm or less, and has easy peelability after heating before and after storage. On the other hand, the peel strength F1 after heating of Comparative Example 1, in which the amount of azo polymerization initiator used relative to 100 parts of the polymer is 0.05 parts, becomes higher, and the easy peelability after heating becomes worse. In addition, in Comparative Example 2, in which only a non-azo polymerization initiator (specifically a peroxide polymerization initiator (NYPER BMT)) is used as a thermal polymerization initiator added to the adhesive, although the peel strength F1 after heating is a low value, the peel strength FS1 after heating after storage at 60°C for 1 week increases. In addition, it can be seen from the comparison between Examples 5 to 7 and Comparative Example 2 that the results of the peel strength FS1 after storage / heating, which is an evaluation item of storage stability, are not correlated with the 10-hour half-life temperature (measured value in a solvent) which is an indicator of the thermal decomposition of the thermal polymerization initiator, but show a tendency to depend on the type of polymerization initiator. It is believed that this is because the thermal decomposition of the thermal polymerization initiator in the adhesive is different from the thermal decomposition in the solvent, and the influence of the properties of the thermal polymerization initiator type is significantly manifested.

[0325] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The technology described in the claims includes examples obtained by variously modifying and changing the specific examples described above.

[0326] Description of Reference Numerals

[0328] 1 Adhesive sheet

[0329] 1A Bonding surface

[0330] 1B Back

[0331] 10. Base material layer

[0332] 10A One side surface

[0333] 10B The other side of the face

[0334] 20 Adhesive layer

[0335] 20A bonding surface

[0336] 30 Release liner

[0337] 50 Adhesive sheet with release liner

Claims

1. An adhesive sheet having an adhesive layer, wherein: The adhesive layer comprises a polymer, a multifunctional monomer and a thermal polymerization initiator, The self-accelerating decomposition temperature (SADT) [°C] of the thermal polymerization initiator satisfies the following formula: SADT+10≥60 The peel force reduction rate after heating A[%] obtained by the following formula is higher than 50% and lower than 99.9%, Reduction rate of peeling force after heating A[%] = (1-F1 / F0) × 100 In the above formula, F1 is the peel strength after heating [N / 20mm] measured at 23°C after being attached to a glass plate and heated at 180°C for 1 hour, and F0 is the peel strength before heating [N / 20mm] on the glass plate.

2. The adhesive sheet according to claim 1, wherein The polymer contains ethylenically unsaturated groups.

3. The adhesive sheet according to claim 1 or 2, wherein The adhesive layer includes a multifunctional acrylate monomer as the multifunctional monomer.

4. The adhesive sheet according to claim 1 or 2, wherein The content of the multifunctional monomer in the adhesive layer is less than 45 parts by weight based on 100 parts by weight of the polymer.

5. The adhesive sheet according to claim 1 or 2, wherein The content of the thermal polymerization initiator in the adhesive layer is 0.1 parts by weight or more based on 100 parts by weight of the polymer.

6. A peeling method, which is a peeling method of the pressure-sensitive adhesive sheet according to claim 1 or 2 adhered to an adherend, the peeling method comprising: The step of subjecting the adherend to which the pressure-sensitive adhesive sheet is attached to the adherend to a heat treatment at a temperature higher than 150° C., and then peeling the pressure-sensitive adhesive sheet from the adherend.

Citation Information

Patent Citations

  • Sheet for fixing semiconductor wafer and chip pick-up method

    JP1998209087A

  • Wafer processing method

    JP2015029105A

  • Thermosetting adhesive composition for adhesive sheet for protecting chemical, adhesive for adhesive sheet for protecting chemical by crosslinking same, adhesive sheet for protecting chemical and application method of adhesive sheet for protecting chemical

    JP2016204617A

  • Double faced adhesive tape, and stacking body of thin film component and supporting component

    JP2019056101A

  • Wire electric discharge machine and wire electric discharge machining method

    JP2022120901A